Hydrogen-sensitive color-changing functional adhesive tape, and preparation method and application thereof
Patent Information
- Application Number
- CN202211222357.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-08
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-10-08
AI Technical Summary
然而,该方法中氢敏材料含量较高,成本相对昂贵
[0050]本发明公开的氢敏变色功能胶带室温对氢气泄漏具有快速、高对比度响应,所述的制备方法简单、高效,在氢气泄漏检测及相关领域具有广阔的应用前景。
Smart Images

Figure CN117887374B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of gas-sensitive sensing technology, specifically to a hydrogen-sensitive color-changing functional tape, its preparation method, and its application. Background Technology
[0002] Hydrogen energy boasts advantages such as being carbon-free, renewable, and highly efficient, making it crucial for my country's efforts to build a "clean, low-carbon, safe, and efficient" modern energy system. In March 2022, my country issued the "Medium- and Long-Term Plan for the Development of the Hydrogen Energy Industry," clearly defining the energy attributes of hydrogen. The transportation sector is currently a major technological area for hydrogen energy application, primarily consisting of fuel cell vehicles and hydrogen refueling stations. Hydrogen refueling stations are critical infrastructure for hydrogen energy applications, and ensuring their safe operation is essential for the healthy and rapid development of the hydrogen energy industry.
[0003] Because hydrogen molecules are small and easily penetrate materials to leak, and because they are colorless and difficult to detect after a leak, a major technical challenge for hydrogen refueling stations is how to effectively detect hydrogen leaks. Typically, hydrogen refueling stations use fixed electrical hydrogen sensors. However, considering the numerous high-pressure hydrogen pipelines and equipment connections, and the rapid diffusion rate of hydrogen, fixed electrical hydrogen sensors are insufficient to effectively detect leaks, let alone accurately locate the leak site. Optical hydrogen leak detection technology based on the hydrogen-chromic mechanism offers a feasible solution to these problems. The main challenge in applying this technology is how to fabricate inorganic functional materials with hydrogen-chromic properties into flexible materials that can be installed and used at hydrogen refueling stations, enabling rapid detection and accurate location of hydrogen leaks.
[0004] Patent CN 109825090 B discloses a hydrogen-sensitive composite silicone material and its preparation method. The method involves drying vinyl silicone rubber, methyl MQ silicone resin, and a zinc oxide and silica compound, followed by the addition of molybdenum oxide, palladium catalyst, hydroxyl silicone oil, and hydrogen-containing silicone oil through open-processing and drying. Molybdenum oxide and palladium catalyst are used as hydrogen-sensitive materials, with a high palladium content (0.5–2 wt.%). The color change time is relatively long, ranging from 49 to 72 seconds, posing a challenge for rapid detection of hydrogen leaks.
[0005] Patent application CN 111662650 A discloses a hydrogen-sensitive color-changing detection tape, its preparation method, and its application. The tape comprises polysiloxane, reinforcing agent, crosslinking agent, crosslinking catalyst, metal oxide, and metal nanoparticles. The raw materials are mixed in a kneader and then extruded through an extruder. The polysiloxane used is a hydroxyl-terminated polysiloxane with a molecular weight of 400,000-600,000. For a hydrogen mixture at a flow rate of 1 L / min, a color change response is observed in 3-10 minutes when the hydrogen concentration is 1 vol.%, and in 1-3 minutes when the hydrogen concentration is 4 vol.%. This method involves adding the metal oxide and metal nanoparticles separately, resulting in a long color-changing time and difficulty in quickly detecting hydrogen leaks.
[0006] Patent application CN 112607779 A discloses a hydrogen-sensitive color-changing tape and its preparation method. The raw material formulation includes a hydrogen-sensitive material and an adhesive. The hydrogen-sensitive material is one or a combination of titanium dioxide and tungsten trioxide hydrogen-sensitive materials, and the adhesive includes polyacrylic acid. Specifically, the titanium dioxide hydrogen-sensitive material comprises tetrabutyl titanate and PdCl2 in a mass ratio of 190-200:1, and the tungsten trioxide hydrogen-sensitive material comprises WO3 and lanthanum nitrate, with a molar ratio of La to W ranging from 1:100 to 1:40. The hydrogen-sensitive material accounts for 10-20% of the total tape volume. However, this method involves a high content of hydrogen-sensitive material, resulting in relatively high costs. Summary of the Invention
[0007] The purpose of this invention is to overcome the problem of existing high-pressure hydrogen-contaminated equipment having numerous connection points and lacking effective rapid detection and accurate positioning hydrogen leakage prevention technology. This invention provides a hydrogen-sensitive color-changing functional tape, its preparation method, and its application. The response time of this hydrogen-sensitive color-changing functional tape to hydrogen can be significantly reduced to ≤30s.
[0008] To achieve the above objectives, the present invention provides a method for preparing a hydrogen-sensitive color-changing functional tape, the method comprising the following steps:
[0009] (1) After mixing polymethylvinylsiloxane with the composite reinforcing agent, kneading and stirring and vacuum degassing are performed, and then cooled and allowed to stand.
[0010] (2) The material obtained in step (1) is mixed with polysilicon boron tackifying resin, hydrogen leak detection material and vinyl polymerization initiator and then subjected to thin-passing, followed by extrusion molding to obtain tape strip semi-finished product;
[0011] (3) Heating and film-coating the semi-finished tape strip obtained in step (2) and then winding it up;
[0012] The composite reinforcing agent contains fumed silica and hydroxyl silicone oil.
[0013] The hydrogen leak detection material comprises a color-changing substrate and an active component; wherein the color-changing substrate is hexagonal tungsten trioxide and has a microstructure of nanorod bundles formed by stacking multiple nanorods; the active component is noble metal nanoparticles; wherein the initial reduction temperature of the hydrogen leak detection material to hydrogen is ≤100℃.
[0014] Preferably, the diameter of the nanorod is 1-10 nm; the length of the nanorod bundle is between 500-1000 nm, and the diameter is between 50-100 nm; the nanorod bundle contains no less than 20 nanorods, and the aspect ratio of the nanorod bundle is 5-20.
[0015] Preferably, the hexagonal tungsten trioxide has (002), (100) and (001) as the main exposed crystal planes, and the intensity of the XRD characteristic diffraction peaks meets the following conditions: I (002) =0.9-1.1×I (100) , and I (002) =1.2-2×I (001) , among which, I (002) I represents the intensity of the characteristic diffraction peak of the (002) crystal plane. (100) I represents the intensity of the characteristic diffraction peak of the (100) crystal plane. (001) The intensity of the diffraction peak of the (001) crystal plane.
[0016] Preferably, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide to visible light in the wavelength range of 400-750 nm, as measured by a spectrometer, is ≥50%, preferably ≥60%, and more preferably ≥65%.
[0017] Preferably, the hexagonal tungsten trioxide has a reflectivity of ≥50% for blue light in the wavelength range of 400-500nm and a reflectivity of ≥70% for red light in the wavelength range of 600-750nm.
[0018] Preferably, the hexagonal tungsten trioxide has a reflectivity of ≥67% for blue light in the wavelength range of 400-500nm and a reflectivity of ≥72% for red light in the wavelength range of 600-750nm.
[0019] Preferably, the noble metal nanoparticles are one or more of platinum nanoparticles, palladium nanoparticles, rhodium nanoparticles and gold nanoparticles, with platinum nanoparticles being the most preferred.
[0020] Preferably, the dispersion of the noble metal nanoparticles on the color-changing substrate is ≥70%, more preferably ≥75%, and even more preferably ≥80%.
[0021] Preferably, the average size of the noble metal nanoparticles is ≤5nm, and more preferably ≤2nm.
[0022] Preferably, the content of the noble metal nanoparticles is 0.1-1.5 wt.%, based on the total weight of the hydrogen leak detection material.
[0023] Preferably, the initial reduction temperature of the hydrogen leak detection material to hydrogen is ≤80℃, and more preferably ≤60℃.
[0024] Preferably, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hydrogen leak detection material measured by a spectrometer for visible light in the wavelength range of 400-750nm is ≥40%, preferably ≥45%.
[0025] Preferably, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hydrogen leak detection material measured by the spectrometer is ≥45% for blue light in the wavelength range of 400-500nm and ≥49% for red light in the wavelength range of 600-750nm.
[0026] Preferably, the hydrogen leak detection material is contacted with hydrogen gas at a concentration of 10 vol.% for 60 seconds to obtain a test sample.
[0027] The difference in reflectance of the test sample to visible light in the wavelength range of 400-750nm is ≥20%;
[0028] Preferably, the difference in reflectance of the test sample to blue light in the wavelength range of 400-500nm is ≥22%, and the difference in reflectance to red light in the wavelength range of 600-750nm is ≥30%.
[0029] Preferably, the color change response time of the hydrogen leak detection material is ≤2s for pure hydrogen, ≤5s for hydrogen with a concentration of 10 vol.%, ≤10s for hydrogen with a concentration of 4 vol.%, ≤13s for hydrogen with a concentration of 2 vol.%, ≤15s for hydrogen with a concentration of 1 vol.%, ≤25s for hydrogen with a concentration of 0.5 vol.%, and ≤50s for hydrogen with a concentration of 0.1 vol.%.
[0030] Preferably, the hydrogen leak detection material has a color change response time of ≤2.5s for hydrogen at a flow rate of 500mL / min at room temperature, ≤3s for hydrogen at a flow rate of 400mL / min, ≤4s for hydrogen at a flow rate of 300mL / min, ≤5s for hydrogen at a flow rate of 200mL / min, ≤8s for hydrogen at a flow rate of 100mL / min, ≤10s for hydrogen at a flow rate of 50mL / min, and ≤20s for hydrogen at a flow rate of 20mL / min.
[0031] Preferably, the hydrogen leak detection material exhibits a color change response time ≤27s for hydrogen at a concentration of 10 vol.% at -25°C, ≤15s for hydrogen at -15°C, ≤13s for hydrogen at -5°C, ≤8s for hydrogen at 5°C, ≤6.5s for hydrogen at 15°C, ≤5s for hydrogen at 25°C, ≤4s for hydrogen at 35°C, and ≤3s for hydrogen at 45°C.
[0032] Preferably, based on a total weight of 100 parts by weight of polymethylvinylsiloxane, composite reinforcing agent, polysilicon-boron tackifying resin, hydrogen leak detection material, and vinyl polymerization initiator, the amount of polymethylvinylsiloxane is 30-80 parts by weight, the amount of composite reinforcing agent is 11-60 parts by weight, the amount of polysilicon-boron tackifying resin is 0.5-8 parts by weight, the amount of hydrogen leak detection material is 1-6 parts by weight, and the amount of vinyl polymerization initiator is 0.2-2 parts by weight.
[0033] Preferably, the amount of fumed silica is 10-50 parts by weight, and the amount of hydroxyl silicone oil is 1-10 parts by weight.
[0034] Preferably, the polymethylvinylsiloxane has a molecular weight of 250,000 to 800,000 and contains 0.01 to 0.35 wt.% vinyl groups.
[0035] Preferably, the specific surface area of the fumed silica is 100-400 m². 2 / g.
[0036] Preferably, the hydroxyl silicone oil contains 2-15 wt.% hydroxyl groups.
[0037] Preferably, the molecular weight of the polysilicon boron tackifying resin is 20,000-140,000, and the polysilicon boron tackifying resin contains 2-20 wt.% boron element.
[0038] Preferably, the vinyl polymerization initiator is selected from one or more of dicumyl peroxide, di-tert-butyl peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0039] Preferably, in step (1), the kneading and mixing time is 15-180 min;
[0040] Preferably, the vacuum degassing conditions include: a temperature of 105-210℃ and a time of 30-360 min;
[0041] Preferably, the settling time is 20-26 hours.
[0042] Preferably, in step (2), the number of thin passes is 2-30;
[0043] Preferably, the thickness of the adhesive tape strip semi-finished product is 0.1-2mm and the width is 0.5-20cm.
[0044] Preferably, step (2) further includes the following step: forming a plurality of grooves on the surface of the adhesive tape semi-finished product.
[0045] Preferably, the groove is shaped like a circle, a square, a rectangle, or a triangle, or two or more of these shapes.
[0046] Preferably, the depth of the groove is 0.001-0.005mm and the spacing is 0.5-5mm.
[0047] Preferably, in step (3), the heating conditions include: a temperature of 250-400℃ and a time of 10-400s.
[0048] A second aspect of the present invention provides a hydrogen-sensitive color-changing functional tape prepared by the above-described preparation method.
[0049] A third aspect of the present invention provides an application of the above-mentioned hydrogen-sensitive color-changing functional tape in hydrogen detection.
[0050] The hydrogen-sensitive color-changing functional tape disclosed in this invention exhibits a rapid and high-contrast response to hydrogen leakage at room temperature. The preparation method described is simple and efficient, and it has broad application prospects in hydrogen leakage detection and related fields. Attached Figure Description
[0051] Figure 1 These are XRD patterns of tungsten trioxide A1 prepared in Example 1 and hydrogen leak detection material B1 prepared in Example 3. Wherein, 1 is the XRD pattern of hydrogen leak detection material B1, and 2 is the XRD pattern of tungsten trioxide A1.
[0052] Figure 2The results are the TPR analysis results of tungsten trioxide A1 prepared in Example 1 and hydrogen leak detection material B1 prepared in Example 3. Wherein, 1 represents the TPR analysis result of the color-changing substrate tungsten trioxide, and 2 represents the TPR analysis result of the hydrogen leak detection material.
[0053] Figure 3 This is a SEM image of tungsten trioxide Al obtained in Example 1.
[0054] Figure 4 This is a TEM image of tungsten trioxide Al obtained in Example 1.
[0055] Figure 5 This is an HRTEM image of tungsten trioxide Al obtained in Example 1.
[0056] Figure 6 This is an HRTEM image of hydrogen leak detection material B1 prepared in Example 3.
[0057] Figure 7 This is an EDS elemental distribution map of hydrogen leak detection material B1 prepared in Example 3. In the image, A is a TEM image, B is a distribution map of tungsten, C is a distribution map of oxygen, and D is a distribution map of platinum. It can be seen that tungsten, oxygen, and platinum are highly uniformly dispersed, and no platinum agglomeration was detected.
[0058] Figure 8 The images show the reflection spectra of tungsten trioxide A1 prepared in Example 1 and the reflection spectra of hydrogen leak detection material B1 prepared in Example 3 before and after being introduced with hydrogen gas at a flow rate of 100 mL / min and a concentration of 10 vol.% at room temperature. 1 is the reflection spectrum of tungsten trioxide A1 prepared in Example 1, 2 is the reflection spectrum of hydrogen leak detection material B1 before hydrogen introduction, and 3 is the reflection spectrum of hydrogen leak detection material B1 after 60 s of hydrogen introduction.
[0059] Figure 9 These are photographs of tungsten trioxide A1 prepared in Example 1 and hydrogen leak detection material B1 prepared in Example 3 before and after being introduced with hydrogen gas at a flow rate of 100 mL / min and a concentration of 10 vol.% at room temperature. In the photographs, A is a photograph of tungsten trioxide A1, B is the hydrogen leak detection material before hydrogen gas is introduced, and C is the hydrogen leak detection material after hydrogen gas is introduced for 60 seconds, and the color is dark blue.
[0060] Figure 10 The graph shows the change in reflectance of hydrogen leak detection material B1 prepared in Example 3 with the time of hydrogen introduction at a H2 concentration of 10 vol.% (hydrogen flow rate 100 mL / min, room temperature). A is the change in reflectance of light at a wavelength of 700 nm with the time of hydrogen introduction, and B is the change in reflectance of light at a wavelength of 475 nm with the time of hydrogen introduction.
[0061] Figure 11 The color change response time of hydrogen leak detection material B1 prepared in Example 3 to hydrogen with different H2 concentrations (flow rate 200 mL / min, room temperature).
[0062] Figure 12 The color change response time of hydrogen leak detection material B1 prepared in Example 3 to hydrogen at different flow rates (H2 concentration of 10 vol.%, room temperature).
[0063] Figure 13 The color change response time of hydrogen leak detection material B1 prepared in Example 3 to hydrogen at different gas temperatures (flow rate 200 mL / min, H2 concentration 10 vol.%). Detailed Implementation
[0064] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0065] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0066] This invention provides a method for preparing hydrogen-sensitive color-changing functional tape, the method comprising the following steps:
[0067] (1) After mixing polymethylvinylsiloxane with the composite reinforcing agent, kneading and stirring and vacuum degassing are performed, and then cooled and allowed to stand.
[0068] (2) The material obtained in step (1) is mixed with polysilicon boron tackifying resin, hydrogen leak detection material and vinyl polymerization initiator and then subjected to thin-passing, followed by extrusion molding to obtain tape strip semi-finished product;
[0069] (3) Heating and film-coating the semi-finished tape strip obtained in step (2) and then winding it up;
[0070] The composite reinforcing agent contains fumed silica and hydroxyl silicone oil.
[0071] The hydrogen leak detection material comprises a color-changing substrate and an active component; wherein the color-changing substrate is hexagonal tungsten trioxide and has a microstructure of nanorod bundles formed by stacking multiple nanorods; the active component is noble metal nanoparticles; wherein the initial reduction temperature of the hydrogen leak detection material to hydrogen is ≤100℃.
[0072] In this invention, the "initial reduction temperature of hydrogen" refers to the initial temperature at which a significant hydrogen consumption peak appears in TPR analysis, obtained using a chemisorption analyzer. The lower the initial reduction temperature of hydrogen, the better the reduction performance of the hydrogen leak detection material.
[0073] In a preferred embodiment of the present invention, the diameter of the nanorod is 1-10 nm; the length of the nanorod bundle is between 500-1000 nm and the diameter is between 50-100 nm; the nanorod bundle contains no less than 20 nanorods and the aspect ratio of the nanorod bundle is 5-20.
[0074] In this invention, the microstructure of the hexagonal tungsten trioxide was obtained by scanning electron microscopy and high-power transmission electron microscopy.
[0075] In this invention, the hexagonal phase of tungsten trioxide is obtained by XRD diffraction pattern.
[0076] In some embodiments of the present invention, the hexagonal tungsten trioxide has (002), (100), and (001) as the main exposed crystal planes, and the intensity of the XRD characteristic diffraction peaks meets the following conditions: I (002) =0.9-1.1×I (100) , and I (002) =1.2-2×I (001) , among which, I (002) I represents the intensity of the characteristic diffraction peak of the (002) crystal plane. (100) I represents the intensity of the characteristic diffraction peak of the (100) crystal plane. (001) The intensity of the diffraction peak of the (001) crystal plane.
[0077] In this invention, unless otherwise specified, the XRD diffraction pattern is obtained by X-ray diffraction.
[0078] The inventors discovered in their research that the degree of exposure of the crystal facets is related to the structure and properties of the formed tungsten trioxide. Using tungsten trioxide with diffraction peak intensity conditions that meet the above requirements as a color-changing substrate, the resulting hydrogen leak detection material changes color faster when exposed to hydrogen and is more sensitive to hydrogen of different concentrations, temperatures, and flow rates.
[0079] In a preferred embodiment of the present invention, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide to visible light in the wavelength range of 400-750 nm, as measured by a spectrometer, is ≥50%, preferably ≥60%, and more preferably ≥65%. More preferably, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide to visible light in the wavelength range of 400-750 nm, as measured by a spectrometer, can be 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95%. For example, among all wavelengths of light in the 400-750nm wavelength range, the reflectance of a certain hexagonal tungsten trioxide is the lowest at 400nm (50%) and the highest at 700nm (70%). Therefore, the reflectance of this hexagonal tungsten trioxide for visible light in the 400-750nm wavelength range is 50-70%.
[0080] It should be noted that the statement that the reflectivity of light within a certain wavelength range is greater than or equal to a certain value refers to the lowest reflectivity among all wavelengths within that wavelength range. For example, if a certain hexagonal tungsten trioxide has the lowest reflectivity (50%) for light at 400 nm within the 400-750 nm wavelength range, then the reflectivity of this hexagonal tungsten trioxide for visible light within the 400-750 nm wavelength range is ≥50%. Similarly, the statement that the reflectivity of light within a certain wavelength range is less than or equal to a certain value refers to the highest reflectivity among all wavelengths within that wavelength range.
[0081] In a preferred embodiment of the present invention, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide for blue light in the wavelength range of 400-500nm is ≥50% and the reflectance for red light in the wavelength range of 600-750nm is ≥70%, as measured by a spectrometer. In a preferred embodiment, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide to blue light in the wavelength range of 400-500 nm, as measured by a spectrometer, can be 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%. The reflectivity of red light in the wavelength range of 600-750nm can be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95%. In a preferred embodiment, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide for blue light in the wavelength range of 400-500nm is ≥67% and the reflectance for red light in the wavelength range of 600-750nm, as measured by a spectrometer, is ≥72%.
[0082] In this invention, unless otherwise specified, the reflectance is obtained by testing with a spectrometer using barium sulfate as the standard (reflectance = 100%). In this invention, unless otherwise specified, "visible light" refers to light in the wavelength range of 400-750 nm; "blue light" refers to light in the wavelength range of 400-500 nm; and "red light" refers to light in the wavelength range of 600-750 nm.
[0083] In this invention, reflectivity refers to the percentage of reflected luminous flux to incident luminous flux that is visible light. Reflectivity corresponds to color and its intensity; higher reflectivity for visible light results in a lighter color. Higher reflectivity for a specific wavelength range also means a higher proportion of that wavelength range in the observed color. In this invention, "blue" refers to a reflectivity of 30-37% for blue light in the 400-500nm wavelength range and 20-30% for red light in the 600-750nm wavelength range. In this invention, "dark blue" refers to a reflectivity of 15-29% for light in the 400-500nm wavelength range and 1-15% for red light in the 600-750nm wavelength range.
[0084] In a preferred embodiment, the noble metal nanoparticles are one or more of platinum nanoparticles, palladium nanoparticles, rhodium nanoparticles, and gold nanoparticles, with platinum nanoparticles being the most preferred.
[0085] In this invention, the noble metal nanoparticles are highly dispersed on the color-changing substrate. In some embodiments of this invention, the dispersion of the noble metal nanoparticles on the color-changing substrate is ≥70%, preferably ≥75%, and more preferably ≥80%. Preferably, the dispersion of the noble metal nanoparticles on the color-changing substrate can be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, or 100%.
[0086] In a preferred embodiment, the average size of the noble metal nanoparticles is ≤5nm, preferably ≤2nm.
[0087] In this invention, the average size of the noble metal nanoparticles was obtained by high-resolution transmission electron microscopy (HRTEM) combined with energy dispersive spectroscopy (ESD).
[0088] In this invention, the dispersion refers to the dispersion performance of noble metal nanoparticles on a color-changing substrate, which is obtained by quantitative hydrogen pulse chemical reaction method.
[0089] In this invention, based on the total weight of the hydrogen leak detection material, the content of the noble metal nanoparticles is 0.1-1.5 wt.%. Specifically, the content of the noble metal nanoparticles can be 0.1 wt.%, 0.2 wt.%, 0.3 wt.%, 0.4 wt.%, 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1 wt.%, 1.1 wt.%, 1.2 wt.%, 1.3 wt.%, 1.4 wt.%, or 1.5 wt.%.
[0090] In this invention, the content of the noble metal nanoparticles is detected by X-ray fluorescence method.
[0091] In some embodiments of the present invention, the initial reduction temperature of the hydrogen leak detection material to hydrogen is ≤80°C, preferably ≤60°C. In specific embodiments, the initial reduction temperature of the hydrogen leak detection material to hydrogen can be 60°C, 55°C, 50°C, 45°C, 40°C, 35°C, 30°C, 25°C, 20°C, 15°C, or 10°C. More preferably, the initial reduction temperature of the hydrogen leak detection material to hydrogen is ≤50°C, more preferably ≤43°C.
[0092] In this invention, when the reflectivity of barium sulfate equals 100% as the standard, the reflectivity of the hydrogen leak detection material to visible light in the 400-750nm wavelength range, as measured by a spectrometer, is ≥40%, preferably ≥45%. Preferably, when the reflectivity of barium sulfate equals 100% as the standard, the reflectivity of the hydrogen leak detection material to visible light in the 400-750nm wavelength range, as measured by a spectrometer, can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, etc. 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95%.
[0093] In this invention, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hydrogen leak detection material measured by the spectrometer is ≥45% for blue light in the wavelength range of 400-500nm and ≥49% for red light in the wavelength range of 600-750nm. In a preferred embodiment, when the reflectance of barium sulfate is equal to 100%, the reflectance of the hydrogen leak detection material to blue light in the wavelength range of 400-500 nm, as measured by a spectrometer, can be 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87 ... The reflectivity of red light in the wavelength range of 600-750nm can be 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95%.
[0094] In this invention, the H2 concentration refers to the percentage of H2 in the total volume of H2 and Ar in an H2 / Ar mixture at room temperature. Different concentrations of hydrogen refer to H2 / Ar mixtures with different H2 concentrations, and vice versa.
[0095] In this invention, "room temperature" refers to "25°C".
[0096] In this invention, the hydrogen leak detection material is contacted with hydrogen gas at a concentration of 10 vol.% for 60 seconds to obtain a test sample. The conditions for introducing the hydrogen gas are: room temperature and a flow rate of 100 mL / min.
[0097] In this invention, when the reflectance of barium sulfate is equal to 100%, the reflectance of the test sample to visible light in the wavelength range of 400-750nm, as measured by a spectrometer, is ≤30%. Preferably, when the reflectance of barium sulfate is equal to 100%, the reflectance of the test sample to visible light in the wavelength range of 400-750nm, as measured by a spectrometer, can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%.
[0098] In this invention, when the reflectance of barium sulfate is 100% as the standard, the reflectance of the test sample, measured by a spectrometer, to blue light in the 400-500nm wavelength range is ≤30%, and the reflectance to red light in the 600-750nm wavelength range is ≤20%. Preferably, when the reflectance of barium sulfate is 100% as the standard, the reflectance of the test sample to blue light in the 400-500nm wavelength range, measured by a spectrometer, can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 2... The reflectance of the sample to red light in the 600-750nm wavelength range can be 0%, 1%, 2%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%, with values of 1%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%. Simultaneously, the difference between the lowest reflectance of the sample to blue light in the 400-500nm wavelength range and the highest reflectance to red light in the 600-750nm wavelength range is ≥5%.
[0099] The method for determining the reflectance of the test sample according to the present invention is as follows: a sample trough with a diameter of 2 cm and a thickness of 1 cm is placed in a sealed gas chamber (10 cm in diameter and 5 cm in thickness). After the hydrogen leakage detection material is placed in the sample trough and ground flat, hydrogen gas with a concentration of 10 vol.% is introduced at room temperature and contacted with the hydrogen leakage detection material for 60 seconds to obtain the test sample. The color change process is tested in real time using a spectrometer to obtain the reflectance data of the test sample.
[0100] In this invention, the difference in reflectance of the test sample to visible light in the 400-750nm wavelength range is ≥20%. Preferably, when the reflectance of barium sulfate is 100%, the difference in reflectance of the test sample to visible light in the 400-750nm wavelength range, measured by a spectrometer, can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, etc. 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, or 94%.
[0101] In this invention, the reflectance variation of the test sample in the 400-500nm wavelength range of blue light has a difference of ≥22%, and the reflectance variation variation in the 600-750nm wavelength range of red light has a difference of ≥30%. Preferably, when the reflectance of barium sulfate is 100%, the reflectance variation variation of the test sample in the 400-500nm wavelength range of blue light, measured by a spectrometer, can be 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, or 45%. 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, The percentages of red light reflectance variation within the 600-750nm wavelength range can be 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95%, with values of 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, and 54%, respectively. 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, or 95%.
[0102] In this invention, the difference in reflectance refers to the difference between the reflectance of the hydrogen leak detection material before and after hydrogen is introduced. Specifically, the difference between the reflectance of the hydrogen leak detection material before and after hydrogen is introduced refers to the difference in the reflectance of the hydrogen leak detection material for the same wavelength before and after hydrogen is introduced. It should be noted that the lowest value of the difference in reflectance of the hydrogen leak detection material for light within a certain wavelength range refers to the lowest value of the difference in reflectance of the hydrogen leak detection material for light within that wavelength range before and after hydrogen is introduced. For example, if a hydrogen leak detection material has a reflectivity of 50-60% for blue light in the 400-500nm wavelength range before hydrogen is introduced, with a reflectivity of 55% for light at a wavelength of 450nm, and a reflectivity of 20-30% for blue light in the 400-500nm wavelength range after hydrogen is introduced, with a reflectivity of 30% for light at a wavelength of 450nm, then the difference in reflectivity of this hydrogen leak detection material for light at a wavelength of 450nm is 25%. If the difference in reflectivity of this material for light at a wavelength of 450nm is lower than the difference in reflectivity of this material for light at other wavelengths in the 400-500nm wavelength range, then the reflectivity of this hydrogen leak detection material for blue light in the 400-500nm wavelength range is ≥25%.
[0103] In some embodiments of the present invention, the color change response time of the hydrogen leak detection material to pure hydrogen is ≤2s, to 10 vol.% hydrogen is ≤5s, to 4 vol.% hydrogen is ≤10s, to 2 vol.% hydrogen is ≤13s, to 1 vol.% hydrogen is ≤15s, to 0.5 vol.% hydrogen is ≤25s, and to 0.1 vol.% hydrogen is ≤50s. The detection conditions for the above color change response time are: at room temperature, the hydrogen flow rate is 200 mL / min. Preferably, the color change response time of the hydrogen leak detection material to pure hydrogen can be any one of 0.5s, 1s, 1.5s, 2s, or a value within the range of any two of the above; the color change response time to 10 vol.% hydrogen can be any one of 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, 5s, or a value within the range of any two of the above; and the color change response time to 4 vol.% hydrogen can be 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, 5s. The color change response time for a 2 vol.% hydrogen gas can be any value within the range of 0.5 s, 1 s, 1.5 s, 2 s, 3 s, 3.5 s, 4 s, 4.5 s, 5 s, 5.5 s, 6 s, 6.5 s, 7 s, 7.5 s, 8 s, 8.5 s, 9 s, 9.5 s, and 10 s, or any combination of two of the above values. The color change response time for a 1 vol.% hydrogen gas is any value within the range of 0.5 s, 1 s, 10 s, 10.5 s, 11 s, 11.5 s, 12 s, 12.5 s, 13 s, or any combination of two of the above values. The color change response times for hydrogen gas with a concentration of 0.5 vol.% are 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s, 3 s, 3.5 s, 4 s, 4.5 s, 5 s, 5.5 s, 6 s, 6.5 s, 7 s, 7.5 s, 8 s, 8.5 s, 9 s, 9.5 s, 10 s, 10.5 s, 11 s, 11.5 s, 12 s, 12.5 s, 13 s, 13.5 s, 14 s, 14.5 s, 15 s, 16 s, and 16 s.The color change response time for 0.1 vol.% hydrogen gas can be any value from 5s, 17s, 17.5s, 18s, 18.5s, 19s, 19.5s, 20s, 20.5s, 21s, 21.5s, 22s, 22.5s, 23s, 23.5s, 24s, 24.5s, 25s, or any combination of two of the above values, and can be 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, 5s, 6s, 7s, 8s, 9s, etc. A value within the range of any one of the following values: 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, 20s, 21s, 22s, 23s, 24s, 25s, 26s, 27s, 28s, 29s, 30s, 31s, 32s, 33s, 34s, 35s, 36s, 37s, 38s, 39s, 40s, 41s, 42s, 43s, 44s, 45s, 46s, 47s, 48s, 49s, and 50s, or any two of the above values.
[0104] In this invention, the "color change response time" refers to the time required for the color of the hydrogen leak detection material to change significantly and noticeably after hydrogen is introduced, corresponding to a 10% difference in reflectance at a wavelength of 700nm.
[0105] In this invention, the method for determining the color change response time of the hydrogen leak detection material is as follows: a sample cell with a diameter of 2 cm and a thickness of 1 cm is placed in a sealed gas chamber (10 cm in diameter and 5 cm in thickness). The hydrogen leak detection material is placed in the sample cell and ground flat. Hydrogen gas under specific conditions is introduced, and the color change process is tested in real time using a spectrometer. That is, the reflectance spectrum data of the hydrogen leak detection material before and during the hydrogen introduction process are recorded in real time, and the color change response time is obtained accordingly, that is, the time required for the difference in reflectance of the hydrogen leak detection material to light at a wavelength of 700 nm to reach 10%.
[0106] In this invention, the hydrogen leak detection material exhibits the following color-changing response times at room temperature: ≤2.5 s for hydrogen at a flow rate of 500 mL / min, ≤3 s for hydrogen at a flow rate of 400 mL / min, ≤4 s for hydrogen at a flow rate of 300 mL / min, ≤5 s for hydrogen at a flow rate of 200 mL / min, ≤8 s for hydrogen at a flow rate of 100 mL / min, ≤10 s for hydrogen at a flow rate of 50 mL / min, and ≤20 s for hydrogen at a flow rate of 20 mL / min. The detection conditions for these color-changing response times are: at room temperature, the hydrogen concentration is 10 vol.%. Preferably, the color change response time of the hydrogen leak detection material at room temperature for hydrogen flow rate of 500 mL / min can be 0.5 s, 1 s, 1.5 s, 2 s, or 2.5 s; for hydrogen flow rate of 400 mL / min, the color change response time can be 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s, or 3 s; and for hydrogen flow rate of 300 mL / min, the color change response time can be 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s, or 3 s. The color change response time for hydrogen gas at a flow rate of 200 mL / min can be 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s, 3 s, 3.5 s, 4 s, 4.5 s, or 5 s. The color change response time for hydrogen gas at a flow rate of 100 mL / min can be 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s, 3 s, 3.5 s, 4 s, 4.5 s, 5 s, 5.5 s, 6 s, 6.5 s, or 7 s. The color change response time for hydrogen gas at a flow rate of 50 mL / min can be 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s, 3 s, 3.5 s, 4 s, 4.5 s, 5 s, 5.5 s, 6 s, 6.5 s, 7 s, 7.5 s, 8 s, 8.5 s, 9 s, 9.5 s, or 10 s. The color change response time for hydrogen gas at a flow rate of 20 mL / min can be 0.5 s, 1 s, 1.5 s, 2 s, or 2.5 s. , 3s, 3.5s, 4s, 4.5s, 5s, 5.5s, 6s, 6.5s, 7s, 7.5s, 8s, 8.5s, 9s, 9.5s, 10s, 10.5s, 11s, 11.5s, 12s , 12.5s, 13s, 13.5s, 14s, 14.5s, 15s, 15.5s, 16s, 16.5s, 17s, 17.5s, 18s, 18.5s, 19s, 19.5s or 20s.
[0107] In this invention, the hydrogen leak detection material exhibits the following color change response times: ≤27 s for hydrogen gas at -25°C with a concentration of 10 vol.%, ≤15 s for hydrogen gas at -15°C, ≤13 s for hydrogen gas at -5°C, ≤8 s for hydrogen gas at 5°C, ≤6.5 s for hydrogen gas at 15°C, ≤5 s for hydrogen gas at 25°C, ≤4 s for hydrogen gas at 35°C, and ≤3 s for hydrogen gas at 45°C. The detection conditions for these color change response times are: a hydrogen gas flow rate of 200 mL / min and a hydrogen gas concentration of 10 vol.%.Preferably, the color change response time of the hydrogen leak detection material to hydrogen gas at a concentration of 10 vol.% at -25°C can be 0.5 s, 1 s, 1.5 s, 2 s, 2.5 s, 3 s, 3.5 s, 4 s, 4.5 s, 5 s, 5.5 s, 6 s, 6.5 s, 7 s, 7.5 s, 8 s, 8.5 s, 9 s, 9.5 s, 10 s, 10.5 s, 11 s, 11.5 s, 12 s, 12.5 s, 13 s, 13.5 s, 14 s, 14.5 s, 15 s, 15.5 s, 16 s, 16.5 s, 17 s, 17.5 s, 18 s, 18.5 s, 19 s. The color change response times to hydrogen gas at -15℃ are 19.5s, 20s, 20.5s, 21s, 21.5s, 22s, 22.5s, 23s, 23.5s, 24s, 24.5s, 25s, 25.5s, 26s, 26.5s, or 27s, with values of 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, 5s, 5.5s, 6s, 6.5s, 7s, 7.5s, 8s, 8.5s, 9s, 9.5s, 10s, 10.5s, 11s, 11.5s, 12s, 12.5s, 13s, 13.5s, and 14s. The color change response time of hydrogen at -5℃ can be 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, 5s, 5.5s, 6s, 6.5s, 7s, 7.5s, 8s, 8.5s, 9s, 9.5s, 10s, 10.5s, 11s, 11.5s, 12s, 12.5s, or 13s. The color change response time of hydrogen at 5℃ can be 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, 5s, 5.5s, 6s, 6.5s, 7s, 7.5s, or 8s. The color change response time for hydrogen at 15℃ can be 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, 5s, 5.5s, 6s, or 6.5s; the color change response time for hydrogen at 25℃ can be 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, or 5s; the color change response time for hydrogen at 35℃ can be 0.5s, 1s, 1.5s, 2s, 2.5s, 3s, 3.5s, or 4s; and the color change response time for hydrogen at 45℃ can be 0.5s, 1s, 1.5s, 2s, 2.5s, or 3s.
[0108] The preparation method of the hydrogen leak detection material of the present invention includes:
[0109] (i) The noble metal precursor, tungsten trioxide and deionized water are first mixed to obtain a solid-liquid mixture;
[0110] (ii) The organic liquid-phase reducing agent is mixed with the solid-liquid mixture for a second time to obtain a reaction mixture;
[0111] (iii) The reaction mixture is subjected to organic liquid-phase reduction;
[0112] The tungsten trioxide is hexagonal tungsten trioxide and has a microstructure of nanorod bundles formed by stacking multiple nanorods.
[0113] In this invention, the amount of the noble metal precursor added is 0.2-5 wt.% of the amount of tungsten trioxide added, preferably 0.5-2 wt.%.
[0114] The inventors discovered in their research that when the amount of the noble metal precursor added exceeds 5 wt.% of the amount of tungsten trioxide added, the noble metal dispersion of the prepared hydrogen leak detection material decreases. Furthermore, when the amount of the noble metal precursor added is 0.5-2 wt.% of the amount of tungsten trioxide added, the noble metal dispersion of the prepared hydrogen leak detection material is higher, exceeding 70%, and it exhibits better hydrogen-sensitive color-changing performance.
[0115] In a preferred embodiment, the amount of the noble metal precursor added, based on the amount of noble metal, can be 0.5 wt.%, 0.6 wt.%, 0.7 wt.%, 0.8 wt.%, 0.9 wt.%, 1 wt.%, 1.5 wt.%, or 2 wt.% of the amount of tungsten trioxide added.
[0116] In this invention, there is no particular limitation on the amount of deionized water added, as long as the solid content in the solid-liquid mixture is 5-70 wt.%.
[0117] In this invention, the added weight of the organic liquid phase reducing agent is 1.5-12 times the added weight of the tungsten trioxide.
[0118] In a preferred embodiment, the added weight of the organic liquid phase reducing agent can be 1.5 times, 2 times, 2.5 times, 3 times, 3.5 times, 4 times, 4.5 times, 5 times, 7 times, 10 times, or 12 times the added weight of the tungsten trioxide.
[0119] In this invention, the noble metal precursor is a soluble salt of a noble metal. Preferably, the soluble salt is a soluble salt of at least one of the noble metals such as platinum, palladium, rhodium, and gold.
[0120] In this invention, the noble metal soluble salt is a platinum soluble salt, such as one or more of potassium chloroplatinate, platinum nitrate, chloroplatinic acid, sodium chloroplatinate, potassium tetranitroplatinate, ammonium chloroplatinate, and potassium chloroplatinate.
[0121] In this invention, the organic liquid-phase reducing agent is an organic alcohol and / or a first organic acid, wherein the first organic acid is one or more of ascorbic acid, oxalic acid and citric acid, and the organic alcohol is one or more of ethylene glycol, propylene glycol and butanediol.
[0122] In hydrogen leak detection materials, increased dispersion of the noble metal nanoparticles on tungsten trioxide helps lower the initial reduction temperature of the material to hydrogen. The inventors have found that when the organic liquid-phase reducing agent is a combination of an organic alcohol and a first organic acid, the resulting hydrogen leak detection material exhibits higher dispersion of the noble metal, further reducing the initial reduction temperature to hydrogen. Therefore, preferably, the organic liquid-phase reducing agent is a combination of an organic alcohol and a first organic acid, with a weight ratio of 1:0.1-5, more preferably 1:0.1-0.3.
[0123] In this invention, there are no requirements regarding the method and time of the first mixing, as long as the noble metal precursor, tungsten trioxide, and deionized water are completely mixed. Preferably, the second mixing method is stirring, and the time is 10-30 minutes.
[0124] In this invention, there are no requirements regarding the method and time of the second mixing, as long as the organic liquid reagent and the solid-liquid mixture are completely mixed. Preferably, the second mixing method is stirring, and the time is 10-30 minutes.
[0125] In this invention, the conditions for the organic liquid phase reduction include: a reduction temperature of 105-180℃, preferably 115-160℃, and a reduction time of 0.5-8h, preferably 1.5-6h.
[0126] In this invention, the inventors discovered that if the reduction temperature is below 105°C, the reduction reaction rate is too low or even cannot occur, making it impossible to deposit metal nanoparticles on tungsten trioxide; if the reduction temperature is above 180°C, the metal reduction rate in the metal-soluble salt will be too fast, causing the metal nanoparticles to agglomerate on the surface of tungsten trioxide. As a result, the metal nanoparticles in the hydrogen leak detection material will have large particle size, poor dispersion, and reduced detection sensitivity.
[0127] In this invention, step (iii) further includes centrifugation, washing, and drying after the organic liquid phase reduction. In some embodiments of this invention, the washing process involves washing with deionized water and anhydrous ethanol. In this invention, there is no requirement for the number of washing cycles, as long as the pH of the washing solution is between 6.5 and 7.5.
[0128] Preferably, the drying conditions are: temperature 60-110℃, time 4-36h. More preferably, the drying conditions are: temperature 80-105℃, time 8-24h.
[0129] In this invention, the method for preparing tungsten trioxide is as follows:
[0130] (a) An inorganic acid, an organic additive, a structure directing agent and a tungsten salt solution are mixed to obtain a mixed solution;
[0131] (b) The mixed solution is subjected to a hydrothermal reaction in a hydrothermal reactor.
[0132] In this invention, the tungsten salt contained in the tungsten salt solution is a tungsten salt that does not contain ammonium ions.
[0133] In this invention, the molar ratio of the number of moles of tungsten in the tungsten salt to the total number of moles of the organic additive and inorganic acid is 0.1-4:1, preferably 0.2-3:1.
[0134] In a preferred embodiment, the molar ratio of the tungsten salt to the total molar ratio of the organic additive and the inorganic acid can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1 or 3:1.
[0135] In this invention, there are no requirements regarding the solvent and volume of the tungsten salt solution, as long as it can dissolve the tungsten salt. Preferably, the solvent for the tungsten salt solution is deionized water.
[0136] In this invention, the molar number of the organic additive is 1-95% of the total molar number of the organic additive and the inorganic acid.
[0137] In a preferred embodiment, the molar percentage of the organic additive as a percentage of the total molar percentage of the organic additive and inorganic acid can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 85%, 90%, or 95%.
[0138] In this invention, the "total number of moles of organic additives and inorganic acids" refers to the sum of the number of moles of organic additives and the number of moles of inorganic acids, and the "number of moles of organic additives" refers to the number of moles of organic additives.
[0139] In this invention, the weight ratio of the tungsten salt to the structure directing agent is 0.1-4:1, preferably 0.2-3:1.
[0140] In a preferred embodiment, the weight ratio of the tungsten salt to the structure directing agent can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.5:1, 2:1, 2.1:1, 2.3:1, 2.5:1, 2.7:1, 2.9:1, or 3:1.
[0141] In this invention, the inorganic acid is at least one of hydrochloric acid, nitric acid, and sulfuric acid.
[0142] In this invention, the organic additive is an organic acid salt and / or a second organic acid. Preferably, the organic acid salt is sodium hexadecylbenzenesulfonate and / or sodium hexadecylsulfonate, and the second organic acid is citric acid and / or oxalic acid.
[0143] In this invention, the structure directing agent is an inorganic structure directing agent, preferably one or more of the chloride, sulfate and nitrate salts of group IA metal elements, more preferably one or more of lithium chloride, sodium chloride, potassium chloride, lithium sulfate, sodium sulfate, lithium bisulfate, sodium bisulfate, potassium bisulfate, lithium nitrate, sodium nitrate and potassium nitrate.
[0144] The inventors unexpectedly discovered during their research that when using tungsten salts containing ammonium ions, such as ammonium metatungstate, the resulting tungsten trioxide did not possess the aforementioned regular nanorod bundle structure and was dark in color. Therefore, in this invention, the tungsten salt is an ammonium-free tungsten salt, preferably one or more of sodium tungstate, phosphotungstic acid, sodium phosphotungstate, lithium tungstate, and potassium tungstate.
[0145] In this invention, the temperature of the hydrothermal reaction is 140-240℃, preferably 150-220℃, and the time is 1-48h, preferably 4-30h.
[0146] In this invention, step (b) further includes centrifugation, washing and drying after the hydrothermal reaction.
[0147] In a preferred embodiment, the washing process involves washing with deionized water and anhydrous ethanol.
[0148] In a preferred embodiment, the drying conditions are: a temperature of 60-120°C and a time of 2-26 hours.
[0149] In this invention, based on a total usage of 100 parts by weight of polymethylvinylsiloxane, composite reinforcing agent, polysilicon-boron tackifying resin, hydrogen leak detection material, and vinyl polymerization initiator, the usage of polymethylvinylsiloxane is 30-80 parts by weight, the usage of composite reinforcing agent is 11-60 parts by weight, the usage of polysilicon-boron tackifying resin is 0.5-8 parts by weight, the usage of hydrogen leak detection material is 1-6 parts by weight, and the usage of vinyl polymerization initiator is 0.2-2 parts by weight; wherein, the usage of fumed silica is 10-50 parts by weight, and the usage of hydroxyl silicone oil is 1-10 parts by weight.
[0150] In this invention, the amount of fumed silica used is 10-50 parts by weight, and the amount of hydroxyl silicone oil used is 1-10 parts by weight. This means that, based on a total amount of 100 parts by weight of polymethylvinylsiloxane, composite reinforcing agent, polysilicon boron tackifying resin, hydrogen leak detection material and vinyl polymerization initiator, the amount of fumed silica used is 10-50 parts by weight, and the amount of hydroxyl silicone oil used is 1-10 parts by weight.
[0151] In this invention, the molecular weight of the polymethylvinylsiloxane can be 250,000 to 800,000, preferably 260,000 to 720,000, and the polymethylvinylsiloxane contains 0.01 to 0.35 wt.% vinyl, preferably 0.02 to 0.25 wt.% vinyl.
[0152] In this invention, the specific surface area of the fumed silica can be 100-400 m². 2 / g, preferably 120-350m 2 / g.
[0153] In this invention, the hydroxyl silicone oil contains 2-15 wt.% hydroxyl groups, preferably 2.2-13.5 wt.% hydroxyl groups.
[0154] In this invention, the molecular weight of the polysilicon boron tackifying resin can be 20,000-140,000, preferably 30,000-120,000, and the polysilicon boron tackifying resin can contain 2-20 wt.% boron, preferably 3.5-16 wt.% boron.
[0155] In this invention, the vinyl polymerization initiator is selected from one or more of dicumyl peroxide (DCP), di-tert-butyl peroxide (DTBP), 2,4-dichlorobenzoyl peroxide (DCBP), and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPMH).
[0156] In a preferred embodiment, in step (1), the kneading and mixing time is 15-180 min, preferably 40-120 min, and more preferably 50-90 min. Specifically, the kneading and mixing time can be 50 min, 60 min, 70 min, 80 min, or 90 min.
[0157] In a preferred embodiment, the vacuum degassing conditions in step (1) include: a temperature of 105-210°C, preferably 125-200°C, and a time of 30-360 min, preferably 40-250 min.
[0158] In this invention, in step (1), the settling time is 20-26 hours. Specifically, the settling time can be 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, or 26 hours.
[0159] In this invention, in step (2), the number of thin passes is 2-30 times, preferably 8-25 times.
[0160] In this invention, the thickness of the adhesive strip semi-finished product is 0.1-2mm, preferably 0.2-1.5mm, and the width is 0.5-20cm, preferably 2-12cm.
[0161] In this invention, to further shorten the color-changing response time to hydrogen, in a preferred embodiment, step (2) further includes the following step: forming a plurality of grooves on the surface of the semi-finished tape strip. The grooves increase the gas diffusion and the contact area with the hydrogen-sensitive color-changing functional tape, which helps to further shorten the color-changing response time to hydrogen.
[0162] In a preferred embodiment, the groove may be one or more of the following shapes: circular, square, rectangular, and triangular.
[0163] In a preferred embodiment of the present invention, the depth of the groove is 0.001-0.005 mm, preferably 0.002-0.004 mm, and the spacing is 0.5-5 mm, preferably 0.5-1.5 mm.
[0164] In this invention, the heating conditions in step (3) include: a temperature of 250-400℃, preferably 280-382℃, and a time of 10-400s, preferably 35-330s.
[0165] A second aspect of the present invention provides a hydrogen-sensitive color-changing functional tape prepared by the above-described preparation method.
[0166] A third aspect of the present invention provides an application of the above-mentioned hydrogen-sensitive color-changing functional tape in hydrogen detection.
[0167] The beneficial effects obtained by this invention are as follows:
[0168] 1. The hexagonal tungsten trioxide used in the hydrogen leak detection material of this invention has a hexagonal crystal internal channel structure that not only has suitable characteristics for the transport of small molecules such as protons and hydrogen, but also has a good promoting effect on the transport of active hydrogen after adsorption and dissociation. Moreover, the unique nanorod bundle microstructure provides diffusion and transport channels for hydrogen and dissociated hydrogen atoms. This invention achieves an effective combination of the hexagonal crystal internal channel structure and the nanorod bundle microstructure, which greatly enhances the color change speed and significantly shortens the color change time.
[0169] 2. Tungsten trioxide with a nanorod bundle microstructure provides an effective carrier structure for the highly uniform dispersion of noble metal nanoparticles. Preferably, the dispersion of the noble metal nanoparticles is ≥70%, and the nanoparticle size is as small as 2 nm, allowing the initial reduction temperature of the hydrogen leak detection material to be reduced to below 60℃. Simultaneously, tungsten trioxide with this structure is white and has a reflectivity of ≥50% for visible light in the 400-750 nm wavelength range, preferably ≥65%. This makes the resulting hydrogen leak detection material more conducive to observing color changes before and after hydrogen flow. The resulting hydrogen-sensitive color-changing functional tape uses a low amount of noble metal, effectively reducing product costs and providing an effective technical solution for hydrogen leak detection.
[0170] 3. The inventors have discovered that hydrogen leak detection materials prepared using tungsten trioxide with the above-mentioned microstructure characteristics (nanoran bundles) have higher sensitivity to hydrogen. Under the same conditions, they have a faster color change response time and a more obvious color change compared to detection materials using tungsten trioxide with other microstructures.
[0171] 4. The hydrogen leak detection material of this invention exhibits a significant change in reflectivity upon contact with hydrogen gas. The difference in reflectivity for visible light in the 400-750nm wavelength range is ≥20%. Compared to existing hydrogen leak detection materials using tungsten oxide as the color-changing substrate, this material achieves a significant color change without the need for a light-colored inert substrate. The difference in reflectivity for blue light in the 400-500nm wavelength range is ≥22%, and the difference in reflectivity for red light in the 600-750nm wavelength range is ≥30%, providing a significant visual alert effect. The color-changing response time for pure hydrogen at room temperature is less than or equal to 2 seconds, and for hydrogen with a 1 vol.% H2 concentration, it is less than or equal to 15 seconds. This significantly shortened color-changing time facilitates rapid detection of hydrogen leak sites.
[0172] 5. The hydrogen leak detection material of the present invention has a fast color change response time for hydrogen at different temperatures, concentrations, and flow rates, and can be applied to different hydrogen leak detection scenarios.
[0173] 6. The method for preparing hydrogen leakage materials in this invention uses an organic liquid-phase reduction method. By controlling the type of organic reagent and the reaction temperature, the noble metal precursor is slowly reduced, avoiding the rapid reduction of noble metals or agglomeration caused by inorganic reducing reagents and high-temperature gas-phase processes. This results in highly dispersed noble metal nanoparticles with superior gas-sensitive color-changing properties.
[0174] 7. This invention uses hydrogen leak detection material as a whole and reacts it with silicone rubber adhesive to prepare hydrogen-sensitive color-changing functional tape. This avoids the technical drawback of adding precious metals and color-changing materials separately to silicone rubber adhesive, which prevents the two components from effectively contacting each other and leads to a long color-changing time. Therefore, the response time of the hydrogen-sensitive color-changing functional tape disclosed in this invention to hydrogen is greatly reduced to ≤30s.
[0175] 8. In this invention, grooves can be further provided on the hydrogen-sensitive color-changing functional tape to increase gas diffusion and the contact area with the hydrogen-sensitive color-changing functional tape, which helps to shorten the color-changing response time to hydrogen.
[0176] 9. The hydrogen-sensitive color-changing functional tape preparation process disclosed in this invention introduces a heating vacuum degassing process, which makes the hydrogen-sensitive color-changing functional tape free of bubble residue, facilitates the contact between gas and active components, and helps to shorten the color-changing response time to hydrogen.
[0177] 10. The present invention uses polymethylvinylsiloxane and composite reinforcing agents (fumed silica and hydroxyl silicone oil) as silicone rubber substrate, which not only gives it good environmental resistance and can be used under extreme conditions of -40 to 120°C and 0 to 100% RH, but also gives it high tensile strength (≥4MPa) and high elongation at break (≥350%).
[0178] 11. This invention uses polysiloxane tackifying resin as a self-adhesive. Due to the structural similarity between the silicon-oxygen bonds in polysiloxane tackifying resin and polymethyl vinyl siloxane, the two can achieve effective contact during the reaction process. Therefore, the hydrogen-sensitive color-changing functional tape of this invention has excellent self-adhesive properties and a self-adhesive strength ≥350g / 2.5cm.
[0179] The present invention will be described in detail below through embodiments, but the scope of the present invention is not limited thereto.
[0180] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are conventional methods. The polymethylvinylsiloxane used in the following examples and comparative examples was purchased from Zhejiang Xin'an Chemical Group Co., Ltd., the fumed silica from Evonik Degussa (A200), the hydroxyl silicone oil from Shanghai Qike Fluorosilicon Materials Co., Ltd., the polysiloxane tackifying resin from Rhodia (Bluestar Group) AD721, and the vinyl polymerization initiator from AkzoNobel PD-50S-PS.
[0181] Room temperature refers to "25℃".
[0182] In the following embodiments and comparative examples:
[0183] The dilute hydrochloric acid, dilute sulfuric acid, and dilute nitric acid were obtained by diluting concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid with deionized water, respectively. Specifically, the concentrated hydrochloric acid was purchased from Sinopharm Reagent Co., Ltd., with a concentration of 37%; the concentrated sulfuric acid was purchased from Sinopharm Reagent Co., Ltd., with a concentration of 98%; and the concentrated nitric acid was purchased from Sinopharm Reagent Co., Ltd., with a concentration of 65%.
[0184] The term "platinum species" refers to species containing the element platinum, such as elements and oxides.
[0185] The H2 concentration refers to the percentage of H2 in the total volume of H2 and Ar in an H2 / Ar mixture at room temperature. Different concentrations of hydrogen refer to H2 / Ar mixtures with different H2 concentrations, and vice versa.
[0186] The XRD diffraction pattern was obtained by testing with an X-ray diffractometer manufactured by Panalytical, Netherlands, with the brand name X'Pert Pro MPD.
[0187] SEM images were obtained using a scanning electron microscope (SEM) purchased from Hitachi, Japan, model number S-4800.
[0188] TEM and HRTEM images were obtained using a high-power transmission electron microscope, and elemental distribution maps were obtained using an energy dispersive spectroscopy (ESD) analyzer attached to the high-power transmission electron microscope. The high-power transmission electron microscope was purchased from JEOL Corporation of Japan, and its model number is JEM-2100.
[0189] The dispersion was obtained through a quantitative hydrogen pulse chemical reaction test using a high-pressure chemical adsorption instrument (HP2950) purchased from Micron Technology, USA. During the test, the hydrogen leak detection material was first reduced to a maximum temperature of 400°C in an H2 / Ar mixed gas at a flow rate of 50 mL / min. Then, it was cooled to room temperature in an inert atmosphere. Finally, a certain amount (0.5 mL) of H2 / Ar mixed gas was continuously pulsed through the instrument, and the hydrogen consumption was calculated using the instrument's built-in algorithm to obtain the dispersion. The hydrogen concentration in the H2 / Ar mixed gas was 10 vol.%. The inert atmosphere was Ar gas.
[0190] TPR analysis was used to determine the initial reduction temperature of the hydrogen leak detection material to hydrogen. The result was obtained using a chemisorption analyzer purchased from Mack Industries, Inc., USA, product code 2950HP. The initial reduction temperature to hydrogen was defined as the temperature at which the first significant hydrogen consumption peak appeared.
[0191] The content of precious metal nanoparticles in the hydrogen leak detection material was determined by X-ray fluorescence analysis. The material was model S8, manufactured by Bruker GmbH, Germany.
[0192] The reflectance spectrum and reflectance were obtained by a spectrometer, specifically the QEPro model manufactured by Marine Optics, Inc., USA. The testing conditions were: barium sulfate reflectance equal to 100% as the standard.
[0193] In the following test, a sample cell with a diameter of 2 cm and a thickness of 1 cm was placed inside a sealed gas chamber (10 cm in diameter and 5 cm in thickness). The hydrogen leak detection material to be tested was placed in the sample cell and smoothed. Hydrogen gas under specific conditions was introduced according to the experimental requirements. The color change process was tested in real time using a spectrometer and a high-speed camera. That is, the reflectance spectrum of the hydrogen leak detection material and the color change data of the hydrogen leak detection material were recorded in real time before and during the hydrogen introduction process, and corresponding analysis was performed.
[0194] 1. By introducing hydrogen gas under specific conditions for a specific period of time, the reflectance spectrum and color of the hydrogen leak detection material before and after the introduction of hydrogen are compared and analyzed to reflect the change in reflectance of the hydrogen leak detection material before and after the introduction of hydrogen.
[0195] 2. Hydrogen leak detection refers to the color change response time of hydrogen leak detection materials to hydrogen with different H2 concentrations, temperatures, and flow rates, which reflects the detection sensitivity of the hydrogen leak detection materials. Specifically, the color change response time refers to the time required for a significant visible color change in the hydrogen leak detection material after hydrogen is introduced, corresponding to a 10% difference in reflectance at a 700nm wavelength.
[0196] The detection effect of hydrogen leak detection materials is reflected by the color change before and after hydrogen flow and the difference in reflectance of visible light in the 400-750nm range. The greater the difference in color and reflectance, the better the hydrogen leak detection material is used to detect hydrogen leaks.
[0197] Example 1
[0198] (1) Weigh a certain amount of sodium tungstate, oxalic acid and sodium sulfate, and measure a 2.5M dilute hydrochloric acid. The specific weighing and measuring amounts are shown in Table 1.
[0199] (2) Dissolve sodium tungstate in 50 mL of deionized water to prepare a sodium tungstate solution. Add dilute hydrochloric acid to the sodium tungstate solution and stir for 25 min. The addition rate of dilute hydrochloric acid is 3 mL / min. After the dilute hydrochloric acid has been completely added, add oxalic acid and sodium sulfate to the above mixed solution and continue stirring for 30 min.
[0200] (3) Transfer the stirred solution to a hydrothermal reactor with a polytetrafluoroethylene liner and a stainless steel outer protective sleeve, tighten it, and then perform a hydrothermal reaction at 160°C for 12 hours, and then let it cool naturally to room temperature.
[0201] (4) The reaction product was centrifuged and washed repeatedly with deionized water and anhydrous ethanol until the pH of the washing solution was between 6.5 and 7. The product was then dried in an oven at 100°C for 12 hours to obtain tungsten trioxide Al.
[0202] The tungsten trioxide Al obtained in Example 1 was analyzed for its crystal phase, microstructure, and reflectance spectrum. The relevant results are as follows: Figure 1 , 3 -5 and Table 2 are shown.
[0203] Figure 1 XRD analysis of tungsten trioxide (Al) and comparison with the standard card (JCPDS 33-1387) revealed that the crystal phase of tungsten trioxide (Al) is hexagonal. Furthermore, the diffraction peak with 2θ around 28° is assigned to the (002) crystal plane, the diffraction peak with 2θ around 22° is assigned to the (100) crystal plane, and the diffraction peak with 2θ around 14° is assigned to the (001) crystal plane. The relative intensities of these three characteristic diffraction peaks satisfy the following:
[0204] I (002) =1.07×I 100) =1.87×I (001)
[0205] Figure 3 , 4 Figures 5 and 6 represent SEM, TEM, and HRTEM analyses of tungsten trioxide (Al), respectively. Figure 3As shown, the microstructure of tungsten trioxide (Al) consists of a bundle of nanorods, each approximately 8 nm in diameter, bonded together and stacked. Figure 4 As shown, the microstructure of tungsten trioxide consists of a bundle of multiple nanorods stacked together. The length of the nanorod bundle is approximately 900 nm, the diameter is approximately 80 nm, and the diameter of a single nanorod is approximately 8 nm. The aspect ratio of the nanorod bundle is 11.25.
[0206] like Figure 8 and Figure 9 As shown, tungsten trioxide (Al) is white, and its reflectance to visible light in the wavelength range of 400-750nm is 68-86%.
[0207] Example 2
[0208] (1) Weigh a certain amount of phosphotungstic acid, sodium hexadecylbenzenesulfonate and lithium sulfate, and measure a certain amount of 0.5M dilute sulfuric acid. The specific weighing and measuring amounts are shown in Table 1.
[0209] (2) Dissolve phosphotungstic acid in 20 mL of deionized water to prepare a phosphotungstic acid solution. Add 0.5 M dilute sulfuric acid to the phosphotungstic acid solution and stir for 20 min. The addition rate of dilute sulfuric acid is 7 mL / min. After the dilute sulfuric acid has been completely added, add sodium hexadecylbenzenesulfonate and lithium sulfate to the above system and continue stirring for 25 min to obtain a mixed solution.
[0210] (3) Transfer the mixed solution to a hydrothermal reactor with a polytetrafluoroethylene liner and a stainless steel outer protective sleeve, tighten it, and then hydrothermally react at 180°C for 20 hours, and then cool it naturally to room temperature.
[0211] (4) The reaction product was centrifuged and washed repeatedly with deionized water and anhydrous ethanol until the pH of the washing solution was between 6.5 and 7. The product was then dried in an oven at 100°C for 9 hours to obtain tungsten trioxide A2.
[0212] Tungsten trioxide (A2) has a hexagonal crystal phase. The diffraction peaks with 2θ around 28° are assigned to the (002) crystal plane, those around 22° to the (100) plane, and those around 14° to the (001) plane. The relative intensities of its diffraction peaks satisfy: I (002) =0.95×I 100) =1.35×I (001) .
[0213] SEM, TEM and HRTEM analyses of tungsten trioxide (A2) revealed that its microstructure consists of a bundle of nanorods, each approximately 6 nm in diameter, stacked together. The bundles are approximately 800 nm long and 60 nm in diameter, with an aspect ratio of 13.33.
[0214] Color analysis and reflectance spectral analysis were performed on tungsten trioxide Al-2. The color of tungsten trioxide Al-2, the reflectance range of visible light in the wavelength range of 400-750nm, the reflectance range of blue light in the wavelength range of 400-500nm, and the reflectance range of red light in the wavelength range of 600-750nm are shown in Table 2.
[0215] Table 1
[0216]
[0217] Note: 1- The molar ratio of tungsten in tungsten salts (total of organic additives and inorganic acids);
[0218] 2- The percentage (%) of organic additives in the total molar amount of organic additives and inorganic acids;
[0219] 3-Tungsten salt: weight ratio of structure-directing agent
[0220] Table 2
[0221]
[0222] As can be seen from Table 2, the tungsten trioxide prepared in Examples 1 and 2 has a microstructure of nanorod bundles, a hexagonal crystal phase, and a reflectivity of >50% for visible light in the wavelength range of 400-750nm. It can be observed that the color is white.
[0223] Example 3
[0224] (1) Accurately weigh 3g of tungsten trioxide Al and 0.03g of chloroplatinic acid. The amount of chloroplatinic acid added is 1wt.% of the amount of tungsten trioxide added. Add them to 50mL of deionized water and stir for 10min to obtain a solid-liquid mixture.
[0225] (2) Weigh 7.5g of ascorbic acid. The weight of ascorbic acid added is 2.5 times the weight of tungsten oxide added. Add it to the solid-liquid mixture and continue stirring for 20 minutes. Then transfer it to a hydrothermal reactor with a polytetrafluoroethylene liner and a stainless steel outer protective sleeve. Tighten the reactor and react at 150℃ for 5 hours. Allow it to cool naturally to room temperature.
[0226] (3) The reaction product was centrifuged and washed repeatedly with deionized water and anhydrous ethanol until the pH of the washing solution was between 6.5 and 7. The product was then dried in an oven at 85°C for 12 hours to obtain hydrogen leak detection material B1.
[0227] X-ray fluorescence analysis of hydrogen leak detection material B1 revealed that the content of platinum nanoparticles on the material was 0.35 wt.%.
[0228] The hydrogen leak detection material prepared in Example 3 was subjected to XRD analysis, TPR analysis, SAED analysis, and HRTEM analysis. The results are as follows: Figure 1-2 ,and Figure 6-7 As shown.
[0229] Figure 1 The XRD analysis results of hydrogen leak detection material B1 are shown in Figure 1, and the XRD analysis results of tungsten trioxide A1 are shown in Figure 2. Comparison with the standard card JCPDS No. 33-1387 reveals that all peaks can be attributed to its color-changing substrate, tungsten trioxide A1, and no diffraction peaks belonging to platinum species were detected. This indicates that the nanoscale size of platinum species is small, exceeding the detection limit of XRD analysis (2-5 nm).
[0230] Figure 2 The TPR analysis results of hydrogen leak detection material B1 are shown. It can be seen that tungsten trioxide (A1) has no H2 adsorption / dissociation ability below 350℃, with a significant hydrogen consumption peak at 490℃. In contrast, hydrogen leak detection material B1 has a significant hydrogen consumption peak at 72℃, with the onset temperature of this peak at 46℃. This indicates that it already possesses hydrogen adsorption / dissociation ability at 46℃, meaning its initial reduction temperature for hydrogen is 46℃, which is below 50℃. This demonstrates that hydrogen leak detection material B1 exhibits significant low-temperature reduction performance, thus facilitating hydrogen adsorption / dissociation and hydrogen-sensitive color-changing reactions at low temperatures and even room temperature.
[0231] Figure 6 The image shown is an HRTEM image of hydrogen leak detection material B1. It can be seen that the microstructure of hydrogen leak detection material B1 is the same as that of tungsten trioxide A1, maintaining the original nanotube bundle microstructure. This indicates that the introduction of noble metal did not change the original micromorphology of tungsten trioxide, and the noble metal nanoparticles were highly dispersed without obvious particle agglomeration.
[0232] Figure 7 The image shows the elemental distribution of hydrogen leak detection material B1. It can be seen that the metallic platinum is highly uniformly dispersed on tungsten trioxide A1, and the size of the platinum nanoparticles is <2nm.
[0233] Hydrogen gas with a concentration of 10 vol.% was introduced at a flow rate of 100 mL / min at room temperature for 60 s. Reflectance spectroscopy and color analysis were performed on the hydrogen leak detection material B1 before and after the hydrogen introduction. The results are as follows: Figure 8-9 As shown. Figure 8 Lines 2 and 3 show the reflectance spectra of hydrogen leakage material B1 before and after hydrogen is introduced, respectively. Figure 9 B and C are photographs comparing hydrogen leak detection material B1 before and after hydrogen flow. Figure 8It can be seen that before hydrogen is introduced, hydrogen leak detection material B1 has a high reflectivity for visible light in the 400-750nm range, within the 45-56% range; its reflectivity for visible light in the 400-500nm wavelength range is ≥45%; and its reflectivity for visible light in the 600-750nm wavelength range is ≥55%. Figure 9 The hydrogen leak detection material B1 in section B is uniformly grayish-white. After introducing hydrogen gas at a concentration of 10 vol.% for 60 seconds, the reflectivity of the hydrogen leak detection material decreased significantly. The reflectivity for visible light in the 400-750 nm wavelength range was 4.9-27%, with higher reflectivity for blue light in the 400-500 nm wavelength range (22-27%), but lower reflectivity for red light in the 600-750 nm wavelength range (4.9-9%). This indicates that after hydrogen introduction, the reflected light from hydrogen leak detection material B1 is predominantly blue, appearing as a deep blue. Furthermore, through… Figure 8 It can be seen that the lowest difference in reflectance of hydrogen leak detection material B1 before and after H2 introduction is greater than 22% for visible light in the 400-750nm wavelength range, greater than 22% for blue light in the 400-500nm wavelength range, and greater than 40% for red light in the 600-750nm wavelength range, corresponding to its significant color change before and after hydrogen introduction. Figure 9 As shown, the hydrogen leak detection material B1 was grayish-white before H2 was introduced and turned dark blue after H2 was introduced, with a significant color contrast. During the process of introducing 10 vol.% hydrogen H2 at a flow rate of 100 mL / min at room temperature, the reflectance spectrum of the hydrogen leak detection material B1 was measured in real time, and the reflectance of material B1 to light at wavelengths of 475 nm and 700 nm was plotted over time. Figure 10 .pass Figure 10 As can be seen, after 5 seconds of hydrogen flow, the reflectivity of hydrogen leak detection material B1 at a wavelength of 475 nm decreased from 53.8% to 53.2%, a difference of 0.6%; the reflectivity at a wavelength of 700 nm decreased from 56% to 47.7%, a difference of 8.3%. This means that after hydrogen flow, the reflectivity of hydrogen leak detection material B1 for blue light decreased more slowly than for red light, indicating that the material reflects more blue light, suggesting a color shift towards blue. Furthermore, it took approximately 6.6 seconds for the reflectivity of the hydrogen leak detection material to reach a 10% change (i.e., a decrease from 56% to 46%) after hydrogen flow, meaning a significant color change was observable after 6.6 seconds.
[0234] Dispersion analysis of hydrogen leak detection material B1 showed that the dispersion of platinum metal on tungsten trioxide was 76%.
[0235] Hydrogen leak detection was performed on hydrogen leak detection material B1, and the specific results are as follows: Figure 11-13 And as shown in Table 3-5:
[0236] 1. Figure 12 The results show the color change response time of hydrogen leak detection material B1 at room temperature for hydrogen gas of different H2 concentrations at a flow rate of 200 mL / min. Figure 11 As shown, for pure H2, the color change response time of the hydrogen leak detection material is <2s; when the H2 concentration is 4 vol.%, the color change response time of the hydrogen leak detection material is <8s; when the H2 concentration is 1 vol.%, the color change response time of the hydrogen leak detection material is <15s; and when the H2 concentration is 0.1 vol.%, the color change response time of the hydrogen leak detection material is approximately 35s.
[0237] 2. Figure 12 The color change response time of hydrogen leak detection material B1 at room temperature to hydrogen gas with a concentration of 10 vol.% and different flow rates is shown. Figure 12 As shown, at a flow rate of 500 mL / min, the color change response time of hydrogen leak detection material B1 is <3 s, and at a flow rate of 200 mL / min, the color change response time of hydrogen leak detection material is <5 s.
[0238] 3. Figure 13 The color change response time of hydrogen leak detection material B1 at different gas temperatures and flow rates of 200 mL / min and H2 concentration of 10 vol.% is shown. Figure 13 As shown, the color change response time of hydrogen leak detection material B1 is approximately 25s for hydrogen at -25℃, <8s for hydrogen at 5℃, and <5s for hydrogen at 25℃.
[0239] The results of the above hydrogen leak detection test show that hydrogen leak detection material B1 has high sensitivity to hydrogen under different conditions. It changes color quickly at room temperature, achieving a rapid response in the second range, and even at low temperatures, the color change response time does not exceed 1 minute.
[0240] Example 4
[0241] (1) Accurately weigh 4.5g of tungsten trioxide A2 and 0.07g of platinum nitrate. The amount of platinum nitrate added is 1.5wt.% of the amount of tungsten trioxide added. Add them to 50mL of deionized water and stir for 10min to obtain a solid-liquid mixture.
[0242] (2) Measure 12 mL of pure ethylene glycol. The weight of ethylene glycol added is 3 times the weight of tungsten oxide added. Add ethylene glycol to the solid-liquid mixture and continue stirring for 20 min. Then transfer it to a hydrothermal reactor with a polytetrafluoroethylene liner and a stainless steel outer protective sleeve. Tighten the reactor and react at 155 °C for 4 h. Allow it to cool naturally to room temperature to obtain the reaction product.
[0243] (3) The reaction product was centrifuged and washed repeatedly with deionized water and anhydrous ethanol until the pH of the washing solution was between 6.5 and 7.0. The product was then dried in an oven at 70°C for 24 hours to obtain hydrogen leak detection material B2.
[0244] X-ray fluorescence analysis of hydrogen leak detection material B2 revealed that the content of platinum nanoparticles on the material was 0.9 wt.%.
[0245] HRTEM images of hydrogen leak detection material B2 show that its microstructure is the same as that of tungsten trioxide A2, maintaining the original nanotube bundle microstructure.
[0246] XRD analysis of hydrogen leak detection material B2 revealed that all peaks could be attributed to its color-changing substrate, tungsten trioxide A2, and no diffraction peaks belonging to platinum species were detected. This indicates that the nanoscale size of platinum species is small, exceeding the detection limit of XRD analysis (2-5 nm).
[0247] Analysis of the elemental distribution of hydrogen leak detection material B2 showed that platinum metal was highly uniformly dispersed on tungsten trioxide A2, and the size of platinum nanoparticles was <2nm.
[0248] Before hydrogen was introduced into the hydrogen leak detection material B2, a reflectance spectrum analysis was performed on it. The reflectance spectrum of the hydrogen leak detection material B2 was observed to be similar to that in Example 3. Figure 12 Similar to line 2. The hydrogen leak detection material B2 has a reflectivity of 45-52% for visible light in the 400-750nm range, a reflectivity of ≥45% for blue light in the 400-500nm range, and a reflectivity of ≥50% for red light in the 600-750nm range.
[0249] Hydrogen gas with a concentration of 10 vol.% was introduced at a flow rate of 100 mL / min at room temperature for 60 s. The reflectance spectrum of the hydrogen leak detection material B2 was then analyzed, and its reflectance spectrum was observed to be similar to that in Example 3. Figure 8Similar to line 3, hydrogen leak detection material B2 has a reflectance range of 5-26% for visible light in the 400-750nm range, 22-26% for blue light in the 400-500nm range, and 5-9% for red light in the 600-750nm range. The lowest difference in reflectance before and after H2 introduction is greater than 22% for visible light in the 400-750nm range, greater than 22% for blue light in the 400-500nm range, and greater than 42% for red light in the 600-700nm range.
[0250] Analysis of the color of hydrogen leak detection material B2 before and after hydrogen flow revealed that it was similar to the color of hydrogen leak detection material B1 before and after hydrogen flow.
[0251] The results of TPR analysis, dispersion analysis, and partial hydrogen leak detection of hydrogen leak detection material B2 are shown in Table 6.
[0252] Hydrogen leak detection was performed on hydrogen leak detection material B2, specifically:
[0253] 1. The detection results of the color change response time of hydrogen gas with different H2 concentrations at a flow rate of 200 mL / min at room temperature are shown in Table 3.
[0254] 2. The detection results of the color change response time of hydrogen gas with a H2 concentration of 10 vol.% and different flow rates at room temperature are shown in Table 4.
[0255] 3. The results of the color change response time of hydrogen at different gas temperatures with a flow rate of 200 mL / min and an H2 concentration of 10 vol.% are shown in Table 5.
[0256] Example 5
[0257] (1) Accurately weigh 3g of tungsten trioxide Al and 0.45g of chloroplatinic acid. The amount of chloroplatinic acid added is 1.5wt.% of the amount of tungsten trioxide added. Add them to 50mL of deionized water and stir for 10min to obtain a solid-liquid mixture.
[0258] (2) Weigh 1.5g of ascorbic acid and 6ml of pure ethylene glycol (the weight ratio of ethylene glycol to ascorbic acid is 1:0.23), add them to the solid-liquid mixture and continue stirring for 20min. Then transfer the mixture to a hydrothermal reactor with a polytetrafluoroethylene liner and a stainless steel outer protective sleeve. Tighten the reactor and react at 140℃ for 5h. Allow it to cool naturally to room temperature.
[0259] (3) The reaction product was centrifuged and washed repeatedly with deionized water and anhydrous ethanol until the pH of the washing solution was between 6.5 and 7. The product was then dried in an oven at 85°C for 12 hours to obtain hydrogen leak detection material B3.
[0260] X-ray fluorescence analysis of hydrogen leak detection material B3 revealed that the content of platinum nanoparticles on the material was 0.97 wt.%.
[0261] HRTEM images of hydrogen leak detection material B3 show that its microstructure is the same as that of tungsten trioxide A1, maintaining the original nanotube bundle microstructure.
[0262] XRD analysis of hydrogen leak detection material B3 revealed that all peaks could be attributed to its color-changing substrate, tungsten trioxide (A1), and no diffraction peaks belonging to platinum species were detected. This indicates that the nanoscale size of platinum species is small, exceeding the detection limit of XRD analysis (2-5 nm).
[0263] Analysis of the elemental distribution of hydrogen leak detection material B3 showed that platinum metal was highly uniformly dispersed on tungsten trioxide Al, and the size of platinum nanoparticles was <2nm.
[0264] Before hydrogen was introduced into the hydrogen leak detection material B3, a reflectance spectrum analysis was performed on it. The reflectance spectrum of the hydrogen leak detection material B3 was observed to be similar to that in Example 3. Figure 12 Line 2 is similar. The hydrogen leak detection material B3 has a reflectance of 46-53% for visible light in the 400-750nm range, a reflectance of ≥46% for blue light in the 400-500nm range, and a reflectance of ≥52% for red light in the 600-750nm range.
[0265] Hydrogen gas with a concentration of 10 vol.% was introduced at a flow rate of 100 mL / min at room temperature for 60 s. The reflectance spectrum of the hydrogen leak detection material B3 was then analyzed, and its reflectance spectrum was observed to be similar to that in Example 3. Figure 8 Similar to line 3, hydrogen leak detection material B3 has a reflectance range of 4.5-26% for visible light in the 400-750nm range, 20-26% for blue light in the 400-500nm range, and 4.5-9% for red light in the 600-700nm range. The lowest difference in reflectance before and after H2 introduction is greater than 22% for visible light in the 400-750nm range, greater than 22% for blue light in the 400-500nm range, and greater than 38% for red light in the 600-750nm range.
[0266] Analysis of the color of hydrogen leak detection material B3 before and after hydrogen flow revealed that it was similar to the color of hydrogen leak detection material B1 before and after hydrogen flow.
[0267] The results of TPR analysis, dispersion analysis, and partial hydrogen leak detection of hydrogen leak detection material B3 are shown in Table 6.
[0268] Hydrogen leak detection was performed on hydrogen leak detection material B3, specifically:
[0269] 1. The detection results of the color change response time of hydrogen gas with different H2 concentrations at a flow rate of 200 mL / min at room temperature are shown in Table 3.
[0270] 2. The detection results of the color change response time of hydrogen gas with a H2 concentration of 10 vol.% and different flow rates at room temperature are shown in Table 4.
[0271] 3. The results of the color change response time of hydrogen at different gas temperatures with a flow rate of 200 mL / min and an H2 concentration of 10 vol.% are shown in Table 5.
[0272] Table 3
[0273]
[0274] Table 4
[0275]
[0276] Table 5
[0277]
[0278] Table 6
[0279] Example 3 76 46 7.2 14.3 Example 4 77 44 7.1 13.5 Example 5 80 40 7 13.2
[0280] Note: *Initial reduction temperature of hydrogen;
[0281] **Color change response time to hydrogen gas at a concentration of 4 vol.% (room temperature, 200 mL / min flow rate);
[0282] *** Color change response time to 1 vol.% hydrogen gas (room temperature, 200 mL / min flow rate).
[0283] As shown in Table 6, the platinum nanoparticles on the hydrogen leak detection materials B1-B3 prepared in Examples 3-5 are highly dispersed on tungsten trioxide, with a dispersion of ≥70%. This contributes to better hydrogen adsorption and dissociation activity of the hydrogen leak detection materials, especially their low-temperature hydrogen adsorption and dissociation activity. The initial reduction temperature (°C) for hydrogen is less than 60°C, and the color change response time for hydrogen with a H2 concentration of 4 vol.% is less than or equal to 10 s, while the color change response time for hydrogen with a H2 concentration of 1 vol.% is less than or equal to 15 s. This demonstrates that hydrogen leak detection materials B1-B3 have high sensitivity to hydrogen. The hydrogen leak detection materials of the present invention significantly shorten the color change time for different hydrogen concentrations.
[0284] Through Example 3 and Figure 8 , Figure 9 It can be seen that the hydrogen leak detection material of the present invention exhibits a large difference in reflectance before and after contact with hydrogen, and a significant color difference, indicating that the hydrogen leak detection material of the present invention has high response efficiency to hydrogen, making it easier for the human eye to identify hydrogen leak sites. Simultaneously, through... Figure 10-13 As can be seen from Tables 3-5, the hydrogen leak detection material prepared by this invention has a fast color change response time for hydrogen with different hydrogen concentrations, different flow rates, and different temperatures. The color change response time does not exceed 1 min under conditions of low hydrogen concentration (as low as 0.1 vol.%), high flow rate (as high as 500 mL / min), or low temperature (as low as -25℃).
[0285] Through Example 3, Figure 2 , Figure 8 , Figure 9 It can be seen that the hydrogen leak detection material made by using hexagonal tungsten trioxide with nanorod bundle structure as color-changing substrate has a lower initial reduction temperature for hydrogen and is more sensitive to hydrogen at different temperatures.
[0286] As can be seen from Table 6, when the amount of precious metal added is within the preferred range of 0.5-2 wt.%, the prepared hydrogen leak detection material has a high dispersion of precious metal, exceeding 70%, and a low initial reduction temperature for hydrogen, exhibiting excellent hydrogen-sensitive color-changing performance.
[0287] As can be seen from Examples 3 and 5, when the organic liquid phase reducing agent is a combination of organic alcohol and first organic acid, the dispersion of noble metal nanoparticles in the prepared hydrogen leak detection material is higher (≥80%), the initial reduction temperature of hydrogen is lower (≤43℃), and the detection sensitivity of the hydrogen leak detection material is better.
[0288] Example 6
[0289] (1) 57.4 parts by weight of polymethylvinylsiloxane (molecular weight of 450,000, vinyl content of 0.15 wt.%) and 29.2 parts by weight of fumed silica (specific surface area of 250 m²) were mixed. 2 The mixture of 4.7 parts by weight of hydroxyl silicone oil (hydroxyl content of 5 wt.%) and 4.7 parts by weight of hydroxyl silicone oil (hydroxyl content of 5 wt.%) was kneaded and stirred at room temperature for 60 min, then degassed under vacuum at 160 °C for 150 min, cooled to room temperature and allowed to stand for 24 h.
[0290] (2) Transfer the material obtained in step (1) to an open mill, and then add 3.7 parts by weight of polysilicon boron tackifying resin (molecular weight of 120,000 and boron content of 10 wt.%), 3.7 parts by weight of hydrogen leak detection material B1 and 1.3 parts by weight of vinyl polymerization initiator (2,4-dichlorobenzoyl peroxide). After mixing, pass through a thin mill 17 times, and then extrude the strip to obtain a tape strip semi-finished product with a thickness of 0.4 mm and a width of 7 cm. Several circular grooves are formed on the surface of the tape strip semi-finished product, with a depth of 0.002 mm and a spacing of 0.7 mm.
[0291] (3) Heat the semi-finished tape strip obtained in step (2) at 365°C for 100 seconds, and then apply film and roll it up to obtain hydrogen-sensitive color-changing functional tape C1.
[0292] Example 7
[0293] The method of Example 6 was implemented, except that the amount of polymethylvinylsiloxane was 49.5 parts by weight, the amount of fumed silica was 35.2 parts by weight, the amount of hydroxyl silicone oil was 6.2 parts by weight, the amount of polysiloxane tackifying resin was 3.9 parts by weight, the amount of hydrogen leak detection material B1 was 3.9 parts by weight, and the amount of vinyl polymerization initiator was 1.3 parts by weight, resulting in hydrogen-sensitive color-changing functional tape C2.
[0294] Example 8
[0295] The method of Example 6 was implemented, except that the amount of polymethylvinylsiloxane was 40 parts by weight, the amount of fumed silica was 43.4 parts by weight, the amount of hydroxyl silicone oil was 7.2 parts by weight, the amount of polysiloxane tackifying resin was 3.9 parts by weight, the amount of hydrogen leak detection material B1 was 4.0 parts by weight, and the amount of vinyl polymerization initiator was 1.5 parts by weight, resulting in hydrogen-sensitive color-changing functional tape C3.
[0296] Example 9
[0297] The method of Example 6 was implemented, except that the amount of polymethylvinylsiloxane was 71.7 parts by weight, the amount of fumed silica was 16.6 parts by weight, the amount of hydroxyl silicone oil was 2.5 parts by weight, the amount of polysiloxane tackifying resin was 3.9 parts by weight, the amount of hydrogen leak detection material B1 was 3.9 parts by weight, and the amount of vinyl polymerization initiator was 1.4 parts by weight, resulting in hydrogen-sensitive color-changing functional tape C4.
[0298] Example 10
[0299] The method of Example 6 was implemented, except that the amount of polymethylvinylsiloxane was 67.2 parts by weight, the amount of fumed silica was 19.6 parts by weight, the amount of hydroxyl silicone oil was 5.5 parts by weight, the amount of polysiloxane tackifying resin was 1.8 parts by weight, the amount of hydrogen leak detection material B1 was 4.3 parts by weight, and the amount of vinyl polymerization initiator was 1.6 parts by weight, resulting in hydrogen-sensitive color-changing functional tape C5.
[0300] Example 11
[0301] The method of Example 6 was implemented, except that the boron content in the polysilicon boron tackifying resin used was 4 wt%, resulting in hydrogen-sensitive color-changing functional tape C5.
[0302] Example 12
[0303] The method of Example 6 was implemented, except that the amount of polymethylvinylsiloxane was 58.2 parts by weight, the amount of fumed silica was 29.8 parts by weight, the amount of hydroxyl silicone oil was 4.8 parts by weight, the amount of polysiloxane tackifying resin was 3.7 parts by weight, the amount of hydrogen leak detection material B1 was 2.1 parts by weight, and the amount of vinyl polymerization initiator was 1.4 parts by weight, resulting in hydrogen-sensitive color-changing functional tape C7.
[0304] Example 13
[0305] The method of Example 6 was implemented, except that the amount of polymethylvinylsiloxane was 56.2 parts by weight, the amount of fumed silica was 28.7 parts by weight, the amount of hydroxyl silicone oil was 4.6 parts by weight, the amount of polysiloxane tackifying resin was 3.6 parts by weight, the amount of hydrogen leak detection material B2 was 5.6 parts by weight, and the amount of vinyl polymerization initiator was 1.3 parts by weight, resulting in hydrogen-sensitive color-changing functional tape C8.
[0306] Example 14
[0307] The method of Example 6 was followed, except that the amount of polymethylvinylsiloxane (molecular weight 320,000, vinyl content 0.06 wt.%) was 54.8 parts by weight, and the amount of fumed silica (specific surface area 300 m²) was [not specified]. 2 The amount of the following components is as follows: 35.2 parts by weight of hydroxyl silicone oil (hydroxyl content of 7.55 wt.%), 3.7 parts by weight of polysiloxane tackifying resin (molecular weight of 90,000, boron content of 12 wt.%), 2.1 parts by weight of hydrogen leak detection material B2, and 0.5 parts by weight of vinyl polymerization initiator (diisopropylbenzene peroxide), to obtain hydrogen-sensitive color-changing functional tape C9.
[0308] Example 15
[0309] The method of Example 6 was followed, except that the amount of polymethylvinylsiloxane (molecular weight 260,000, vinyl content 0.15 wt.%) was 55.4 parts by weight, and the amount of fumed silica (specific surface area 150 m²) was [not specified in the original text]. 2 The amount of the following components is as follows: 30.0 parts by weight of hydroxyl silicone oil (hydroxyl content of 3.2 wt.%), 3.7 parts by weight of polysiloxane tackifying resin (molecular weight of 40,000, boron content of 3.6 wt.%), 4.0 parts by weight of hydrogen leak detection material B1, and 0.8 parts by weight of vinyl polymerization initiator (di-tert-butyl peroxide), to obtain hydrogen-sensitive color-changing functional tape C10.
[0310] Example 16
[0311] The method of Example 6 was followed, except that the amount of polymethylvinylsiloxane (molecular weight 720,000, vinyl content 0.04 wt.%) was 67.2 parts by weight, and the amount of fumed silica (specific surface area 130 m²) was [not specified in the original text]. 2 The amount of the following components is as follows: 19.6 parts by weight of hydroxyl silicone oil (hydroxyl content of 2.2 wt.%), 2.7 parts by weight of polysiloxane tackifying resin (molecular weight of 30,000, boron content of 7.5 wt.%), 5.5 parts by weight of hydrogen leak detection material B3, and 0.7 parts by weight of vinyl polymerization initiator (2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane), to obtain hydrogen-sensitive color-changing functional tape C11.
[0312] Example 17
[0313] The method of Example 6 was followed, except that the amount of polymethylvinylsiloxane (molecular weight 670,000, vinyl content 0.22 wt.%) was 56.6 parts by weight, and the amount of fumed silica (specific surface area 270 m²) was [not specified].2 The amount of the following components is as follows: 31.7 parts by weight of hydroxyl silicone oil (hydroxyl content of 13.2 wt.%), 6.4 parts by weight of polysiloxane tackifying resin (molecular weight of 70,000, boron content of 16 wt.%), 1.9 parts by weight of hydrogen leak detection material B3, and 0.8 parts by weight of vinyl polymerization initiator (2,4-dichlorobenzoyl peroxide), to obtain hydrogen-sensitive color-changing functional tape C12.
[0314] Example 18
[0315] (1) 56.6 parts by weight of polymethylvinylsiloxane (molecular weight of 670,000, vinyl content of 0.22 wt.%) and 31.6 parts by weight of fumed silica (specific surface area of 270 m²) were mixed. 2 The mixture of 6.4 parts by weight of hydroxyl silicone oil (hydroxyl content of 13.2 wt.%) and 6.4 parts by weight of hydroxyl silicone oil (hydroxyl content of 13.2 wt.%) was kneaded and stirred at room temperature for 60 min, then degassed under vacuum at 125 °C for 250 min, cooled to room temperature and allowed to stand for 24 h.
[0316] (2) Transfer the material obtained in step (1) to an open mill, and then add 2.6 parts by weight of polysilicon boron tackifying resin (molecular weight of 120,000 and boron content of 10 wt.%), 2.0 parts by weight of hydrogen leak detection material B1 and 0.8 parts by weight of vinyl polymerization initiator (2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane). After mixing, pass through a thin tube 8 times, and then extrude the strip to obtain a tape strip semi-finished product with a thickness of 0.3 mm and a width of 12 cm. Several rectangular grooves are formed on the surface of the tape strip semi-finished product. The grooves are 0.003 mm deep and 0.6 mm apart.
[0317] (3) Heat the semi-finished tape strip obtained in step (2) at 280°C for 330s, and then apply film and roll it up to obtain hydrogen-sensitive color-changing functional tape C13.
[0318] Example 19
[0319] (1) 56.6 parts by weight of polymethylvinylsiloxane (molecular weight of 670,000, vinyl content of 0.22 wt.%) and 31.6 parts by weight of fumed silica (specific surface area of 270 m²) were mixed. 2 / g) and 6.4 parts by weight of hydroxyl silicone oil (hydroxyl content is 13.2wt.%), kneaded and stirred for 60 min, then degassed under vacuum at 200℃ for 40 min, cooled to room temperature and allowed to stand for 24 h;
[0320] (2) Transfer the material obtained in step (1) to an open mill, and then add 2.6 parts by weight of polysilicon boron tackifying resin (molecular weight of 120,000 and boron content of 10 wt.%), 2.0 parts by weight of hydrogen leak detection material B1 and 0.8 parts by weight of vinyl polymerization initiator (di-tert-butyl peroxide). After mixing, pass through a thin mill 25 times, and then extrude the strip to obtain a tape strip semi-finished product with a thickness of 1.5 mm and a width of 5 cm. Several triangular grooves are formed on the surface of the tape strip semi-finished product. The grooves are 0.002 mm deep and 1.5 mm apart.
[0321] (3) Heat the semi-finished tape strip obtained in step (2) at 320°C for 180s, and then apply film and roll it up to obtain hydrogen-sensitive color-changing functional tape C14.
[0322] Example 20
[0323] (1) 56.6 parts by weight of polymethylvinylsiloxane (molecular weight of 670,000, vinyl content of 0.22 wt.%) and 31.6 parts by weight of fumed silica (specific surface area of 270 m²) were mixed. 2 The mixture of 6.4 parts by weight of hydroxyl silicone oil (hydroxyl content of 13.2 wt.%) and 6.4 parts by weight of hydroxyl silicone oil (hydroxyl content of 13.2 wt.%) was kneaded and stirred at room temperature for 60 min, then degassed under vacuum at 185 °C for 110 min, cooled to room temperature and allowed to stand for 24 h.
[0324] (2) Transfer the material obtained in step (1) to an open mill, and then add 2.6 parts by weight of polysilicon boron tackifying resin (molecular weight of 120,000 and boron content of 10 wt.%), 2.0 parts by weight of hydrogen leak detection material B1 and 0.8 parts by weight of vinyl polymerization initiator (diisopropylbenzene peroxide). After mixing, pass through a thin mill 15 times, and then extrude the strip to obtain a tape strip semi-finished product with a thickness of 0.2 mm and a width of 2 cm. Several circular and triangular alternating grooves are formed on the surface of the tape strip semi-finished product. The grooves are 0.004 mm deep and 0.5 mm apart.
[0325] (3) Heat the semi-finished tape strip obtained in step (2) at 382°C for 35 seconds, and then apply film and roll it up to obtain hydrogen-sensitive color-changing functional tape C15.
[0326] Example 21
[0327] The method of Example 6 is implemented, except that in step (2), no groove is formed on the surface of the tape strip semi-finished product to obtain hydrogen-sensitive color-changing functional tape C16.
[0328] Comparative Example 1
[0329] The method of Example 6 was implemented, except that in step (1), vacuum degassing was not performed, and the kneaded and stirred material was directly left to stand at room temperature for 24 hours to finally obtain hydrogen-sensitive color-changing functional tape D1.
[0330] Comparative Example 2
[0331] The method of Example 6 is implemented, except that in step (3), the tape strip semi-finished product obtained in step (2) is not heated, but directly laminated and rolled up to obtain hydrogen-sensitive color-changing functional tape D2.
[0332] Comparative Example 3
[0333] The method of Example 6 was implemented, except that in step (2), the hydrogen leak detection material B1 was replaced with tungsten trioxide A1 and chloroplatinic acid, wherein the total amount of tungsten trioxide A1 and chloroplatinic acid was the same as the amount of hydrogen leak detection material B1, and the amount of chloroplatinic acid was 1 wt.% of the amount of tungsten trioxide A1, thus obtaining hydrogen-sensitive color-changing functional tape D3.
[0334] Comparative Example 4
[0335] The method of Example 6 was implemented, except that in step (2), the hydrogen leak detection material B1 was replaced with commercially available tungsten trioxide (purchased from Sinopharm Reagent Company, analytical grade reagent, monoclinic phase) and chloroplatinic acid. The total amount of commercially available tungsten trioxide and chloroplatinic acid was the same as the amount of hydrogen leak detection material B1, and the amount of chloroplatinic acid was 1 wt.% of the amount of commercially available tungsten trioxide, resulting in hydrogen-sensitive color-changing functional tape D4.
[0336] Test Example 1
[0337] The tensile strength, elongation at break, self-adhesion, presence or absence of blistering, environmental adaptability, and response time to hydrogen color change were tested for C1-C16 and D1-D4.
[0338] Tensile strength and elongation at break were tested using the national standard GB / T 528-2009 "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber" on a universal testing machine (MTS Exceed E43).
[0339] The self-adhesive test method is to fold the hydrogen-sensitive functional tape completely in half, roll it back and forth four times with a pressure roller, leave it for 3 minutes, and then fix the non-overlapping ends of the test piece onto the fixture of a universal tensile testing machine. The testing machine runs at a speed of 300 mm / min and records the tensile force required to completely separate the overlapping parts.
[0340] The presence or absence of bubbles is determined through observation.
[0341] The environmental adaptability testing method is based on the national standard GB / T 18244-2000 "Aging Test Method for Building Waterproofing Materials" and is carried out on Q-SUN equipment.
[0342] The method for detecting the hydrogen color-changing response time is as follows: A sample cell with a diameter of 2cm and a thickness of 1cm is placed in a sealed gas chamber (10cm in diameter and 5cm in thickness). The hydrogen-sensitive color-changing functional tape is placed in the sample cell and leveled. Hydrogen gas under specific conditions (200ml / min) is introduced at room temperature. The color-changing process is tested in real time using a spectrometer, that is, the reflectance spectrum data of the hydrogen-sensitive color-changing functional tape before and during the hydrogen introduction are recorded in real time. The color-changing response time is then obtained, which is the time required for the difference in reflectance of the hydrogen-sensitive color-changing functional tape to reach 10% at a wavelength of 700nm.
[0343] The results are shown in Table 7.
[0344] Table 7
[0345]
[0346]
[0347] As can be seen from the results in Table 7, the present invention uses hydrogen leak detection material as a whole and reacts it with silicone rubber adhesive to prepare hydrogen-sensitive color-changing functional tape, which greatly reduces the response time to 10 vol.% hydrogen to ≤30s. At the same time, it also has high self-adhesion, tensile strength and elongation at break, and good environmental resistance.
[0348] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing a hydrogen-sensitive color-changing functional adhesive tape, characterized in that, The method includes the following steps: (1) After mixing polymethylvinylsiloxane with the composite reinforcing agent, knead and stir and vacuum degas, then let it stand after cooling; (2) The material obtained in step (1) is mixed with polysilicon boron tackifying resin, hydrogen leak detection material and vinyl polymerization initiator and then subjected to thin-passing, followed by extrusion molding to obtain tape strip semi-finished product; (3) Heating and film-coating the semi-finished tape strip obtained in step (2) and then winding it up; The composite reinforcing agent contains fumed silica and hydroxyl silicone oil; the polymethylvinylsiloxane has a molecular weight of 250,000-800,000 and contains 0.01-0.35 wt.% vinyl groups. The hydrogen leak detection material comprises a color-changing substrate and an active component; wherein the color-changing substrate is hexagonal tungsten trioxide and has a microstructure of nanorod bundles formed by stacking multiple nanorods; the active component is noble metal nanoparticles, and the dispersion of the noble metal nanoparticles on the color-changing substrate is ≥70%; wherein the initial reduction temperature of the hydrogen leak detection material to hydrogen is ≤100℃.
2. The preparation method according to claim 1, characterized in that, The diameter of the nanorods is 1-10 nm; the length of the nanorod bundle is between 500-1000 nm and the diameter is between 50-100 nm; the nanorod bundle contains no less than 20 nanorods and the aspect ratio of the nanorod bundle is 5-20.
3. The preparation method according to claim 1 or 2, characterized in that, The hexagonal tungsten trioxide has (002), (100), and (001) as its main exposed crystal planes, and the intensity of its XRD characteristic diffraction peaks meets the following conditions: I (002) =0.9-1.1×I (100) , and I (002) =1.2-2×I (001) , among which, I (002) I represents the intensity of the characteristic diffraction peak of the (002) crystal plane. (100) I represents the intensity of the characteristic diffraction peak of the (100) crystal plane. (001) The intensity of the diffraction peak of the (001) crystal plane.
4. The preparation method according to claim 1 or 2, characterized in that, When the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide in the visible light range of 400-750nm, as measured by a spectrometer, is ≥50%.
5. The preparation method according to claim 4, characterized in that, When the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide in the visible light range of 400-750nm, as measured by a spectrometer, is ≥60%.
6. The preparation method according to claim 5, characterized in that, When the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide in the visible light range of 400-750nm, as measured by a spectrometer, is ≥65%.
7. The preparation method according to claim 1 or 2, characterized in that, When the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide in the wavelength range of 400-500nm is ≥50% and the reflectance of the wavelength range of 600-750nm is ≥70%, as measured by a spectrometer.
8. The preparation method according to claim 7, characterized in that, When the reflectance of barium sulfate is equal to 100%, the reflectance of the hexagonal tungsten trioxide in the wavelength range of 400-500nm is ≥67% and the reflectance of the red light in the wavelength range of 600-750nm is ≥72%, as measured by a spectrometer.
9. The preparation method according to claim 1 or 2, characterized in that, The precious metal nanoparticles are one or more of platinum nanoparticles, palladium nanoparticles, rhodium nanoparticles, and gold nanoparticles.
10. The preparation method according to claim 1 or 2, characterized in that, The noble metal nanoparticles are platinum nanoparticles.
11. The preparation method according to claim 1 or 2, characterized in that, The dispersion of the noble metal nanoparticles on the color-changing substrate is ≥75%.
12. The preparation method according to claim 1 or 2, characterized in that, The dispersion of the noble metal nanoparticles on the color-changing substrate is ≥80%.
13. The preparation method according to claim 1 or 2, characterized in that, The average size of the noble metal nanoparticles is ≤5 nm.
14. The preparation method according to claim 1 or 2, characterized in that, The average size of the noble metal nanoparticles is ≤2 nm.
15. The preparation method according to claim 1 or 2, characterized in that, Based on the total weight of the hydrogen leak detection material, the content of the precious metal nanoparticles is 0.1-1.5 wt.%.
16. The preparation method according to claim 1 or 2, characterized in that, The hydrogen leak detection material has an initial reduction temperature of ≤80℃ for hydrogen.
17. The preparation method according to claim 1 or 2, characterized in that, The hydrogen leak detection material has an initial reduction temperature of ≤60℃ for hydrogen.
18. The preparation method according to claim 1 or 2, characterized in that, When the reflectivity of barium sulfate is equal to 100%, the reflectivity of the hydrogen leak detection material in the visible light range of 400-750nm, as measured by a spectrometer, is ≥40%.
19. The preparation method according to claim 1, characterized in that, When the reflectivity of barium sulfate is equal to 100%, the reflectivity of the hydrogen leak detection material in the visible light range of 400-750nm, as measured by a spectrometer, is ≥45%.
20. The preparation method according to claim 1, characterized in that, When the reflectivity of barium sulfate is equal to 100%, the reflectivity of the hydrogen leak detection material measured by the spectrometer is ≥45% for blue light in the wavelength range of 400-500nm and ≥49% for red light in the wavelength range of 600-750nm.
21. The preparation method according to claim 19 or 20, characterized in that, The hydrogen leak detection material was contacted with hydrogen gas at a concentration of 10 vol.% for 60 seconds to obtain a test sample; The difference in reflectance of the test sample in the visible light wavelength range of 400-750nm is ≥20%.
22. The preparation method according to claim 21, characterized in that, The test sample showed a reflectance variation of ≥22% for blue light in the 400-500nm wavelength range and a reflectance variation of ≥30% for red light in the 600-750nm wavelength range.
23. The preparation method according to claim 1, characterized in that, Based on a total usage of 100 parts by weight of polymethylvinylsiloxane, composite reinforcing agent, polysilicon-boron tackifying resin, hydrogen leak detection material, and vinyl polymerization initiator, the usage of polymethylvinylsiloxane is 30-80 parts by weight, the usage of composite reinforcing agent is 11-60 parts by weight, the usage of polysilicon-boron tackifying resin is 0.5-8 parts by weight, the usage of hydrogen leak detection material is 1-6 parts by weight, and the usage of vinyl polymerization initiator is 0.2-2 parts by weight.
24. The preparation method according to claim 1 or 23, characterized in that, Based on a total usage of 100 parts by weight of polymethylvinylsiloxane, composite reinforcing agent, polysilicon-boron tackifying resin, hydrogen leak detection material and vinyl polymerization initiator, the usage of fumed silica is 10-50 parts by weight and the usage of hydroxyl silicone oil is 1-10 parts by weight.
25. The preparation method according to claim 1 or 23, characterized in that, The specific surface area of the fumed silica is 100-400 m². 2 / g.
26. The preparation method according to claim 1 or 23, characterized in that, The hydroxyl silicone oil contains 2-15 wt.% hydroxyl groups.
27. The preparation method according to claim 1 or 23, characterized in that, The molecular weight of the polysilicon boron tackifying resin is 20,000-140,000, and the polysilicon boron tackifying resin contains 2-20 wt.% boron element.
28. The preparation method according to claim 1 or 23, characterized in that, The vinyl polymerization initiator is selected from one or more of dicumyl peroxide, di-tert-butyl peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
29. The preparation method according to claim 1 or 23, characterized in that, In step (1), the kneading and mixing time is 15-180 min.
30. The preparation method according to claim 1 or 23, characterized in that, The conditions for vacuum degassing include: a temperature of 105-210℃ and a time of 30-360 min.
31. The preparation method according to claim 1 or 23, characterized in that, The settling time is 20-26 hours.
32. The preparation method according to claim 1 or 2, characterized in that, In step (2), the number of times the thin tube is passed is 2-30 times.
33. The preparation method according to claim 1 or 2, characterized in that, The thickness of the semi-finished tape strip is 0.1-2 mm, and the width is 0.5-20 cm.
34. The preparation method according to claim 1 or 2, characterized in that, Step (2) also includes the following step: forming several grooves on the surface of the tape strip semi-finished product.
35. The preparation method according to claim 34, characterized in that, The groove is shaped like a circle, a square, a rectangle, or a triangle, or two or more of these shapes.
36. The preparation method according to claim 34, characterized in that, The grooves have a depth of 0.001-0.005 mm and a spacing of 0.5-5 mm.
37. The preparation method according to claim 1 or 2, characterized in that, In step (3), the heating conditions include: a temperature of 250-400℃ and a time of 10-400 s.
38. The hydrogen-sensitive color-changing functional tape prepared by the preparation method according to any one of claims 1-37.
39. The application of the hydrogen-sensitive color-changing functional tape according to claim 38 in hydrogen detection.
Citation Information
Patent Citations
A hydrogen-sensitive composite silica gel material and its preparation method
CN109825090B
Hydrogen-sensitive discoloration detection adhesive tape, and preparation method and application thereof
CN111662650A
Hydrogen-sensitive color-changing adhesive tape and preparation method thereof
CN112607779A